Multi-block copolymer, photoresist composition including the same, and pattern forming method
By using multi-block copolymers in the photolithographic patterning, the problems of insufficient resolution and high LWR of the existing photoresist compositions at sizes less than 60 nm are solved, and higher pattern accuracy and high integration density of semiconductor devices are achieved.
Patent Information
- Application Number
- CN202411394523.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-04
- Filing Date
- 2024-10-08
- Publication Date
- 2025-04-08
AI Technical Summary
The existing photoresist compositions have problems such as insufficient resolution and high linewidth roughness (LWR) in the photolithographic patterning at a critical size of less than 60 nm, which affects the integration density and structural accuracy of semiconductor devices.
Using a multi-block copolymer as the main component of the photoresist composition, by introducing multiple blocks into the polymer chain, each block containing repeat units of different structures, ensures that the repeat units of the polymer chain are distributed substantially uniformly along the entire main chain.
The resolution of lithographic patterning is improved and the LWR is reduced, pattern accuracy in the nanometer range is enhanced, and high-yield manufacturing of semiconductor devices is supported.
Smart Images

Figure BDA0005073389050000101 
Figure BDA0005073389050000121 
Figure BDA0005073389050000131
Abstract
Description
Technical Field
[0001] The present invention relates to multi-block copolymers for use in photoresist compositions and pattern forming methods using such photoresist compositions. The present invention is suitable for photolithography applications in the semiconductor manufacturing industry. Background Art
[0002] Photoresist materials are photosensitive compositions typically used to transfer an image to one or more underlying layers, such as metal, semiconductor or dielectric layers, disposed on a semiconductor substrate. In order to increase the integration density of semiconductor devices and allow the formation of structures with dimensions in the nanometer range, photoresists and photolithography processing tools with high-resolution capabilities have been and continue to be developed.
[0003] State-of-the-art lithography patterning processes currently employ ArF (193nm) immersion scanners to process wafers with dimensions less than 60 nanometers (nm). Pushing ArF lithography to critical dimensions less than 60nm poses several challenges to the capabilities of photoresists in terms of process window, line width roughness (LWR), and other key parameters for large-scale integrated circuit manufacturing. All of these parameters must be addressed in next-generation formulations. As pattern dimensions decrease in advanced nodes, LWR values do not decrease simultaneously at the same rate, creating a significant source of variation during processing at these leading-edge nodes. Improvements in process windows are also useful in achieving high yields in integrated circuit manufacturing.
[0004] Extreme ultraviolet lithography (EUV lithography) is another leading technology for large-scale semiconductor wafer manufacturing at critical dimensions below 20 nm.
[0005] Photoresist polymers are commonly used in photoresist compositions to achieve useful properties during photolithographic processing. However, when using polymers prepared by conventional methods, the uneven distribution of polymer functionality between polymer chains and / or variations along the polymer backbone can present challenges when attempting to pattern at higher resolutions.
[0006] There remains a continuing need for photoresist compositions that address one or more problems associated with photolithographic patterning at critical dimensions less than 60 nm. In particular, there continues to be a need for photoresist compositions that can achieve improved resolution and reduced LWR. Summary of the invention
[0007] On the one hand, a block copolymer is provided, which comprises: a first block, which comprises two or more structurally different repeating units; a second block, which comprises two or more structurally different repeating units; the repeating units of the first block comprise acid-labile groups, lactone groups, salt groups, or hydroxyaryl groups; and the repeating units of the second block comprise acid-labile groups, lactone groups, salt groups, or hydroxyaryl groups, wherein the two or more structurally different repeating units of the first block are the same as the two or more structurally different repeating units of the second block.
[0008] Another aspect provides a polymer comprising one or more block copolymers as described herein bonded to another portion of the polymer.
[0009] Yet another aspect provides a photoresist composition comprising the block copolymer as provided herein and a solvent.
[0010] Another aspect provides a pattern forming method comprising forming a photoresist composition layer from a photoresist composition on a substrate, exposing the photoresist composition layer to activating radiation in a pattern manner, and developing the exposed photoresist composition layer to provide a resist relief image. DETAILED DESCRIPTION
[0011] Reference will now be made in detail to exemplary embodiments, examples of which are shown in this specification. In this regard, exemplary embodiments of the present invention may have different forms and should not be construed as being limited to the description described herein. Therefore, exemplary embodiments are only described below to explain aspects of this specification. As used herein, the term "and / or" includes any and all combinations of one or more of the related listed items. When a statement such as "at least one / kind of ... " is before an element list, it modifies the entire element list and does not modify a single element in the list.
[0012] As used herein, the terms "a / an" and "the" do not represent a limit to quantity, and unless otherwise indicated herein or clearly contradictory to the context, are interpreted as including both the singular and the plural. Unless otherwise explicitly stated, "or" means "and / or". The modifier "about" used in conjunction with the quantity includes the value and has the meaning specified by the context (e.g., including the degree of error associated with the measurement of a specific quantity). The full range disclosed herein includes endpoints, and these endpoints are independently combinable with each other. The suffix "(s)" is intended to include both the singular and the plural of the term it modifies, thereby including at least one of the term. "Optional" or "optionally" means that the event or situation described subsequently may or may not occur, and the description includes the situation in which the event occurs and the situation in which it does not occur. The terms "first", "second" and similar terms do not represent order, quantity, or importance in this article, but are used to distinguish one element from another. When an element is referred to as "on" another element, it may be in direct contact with the other element or an intervening element may be present therebetween. In contrast, when an element is referred to as being "directly on" another element, there are no intervening elements present. It will be appreciated that the components, elements, limitations and / or features of the described aspects may be combined in any suitable manner among the various aspects.
[0013] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. It will be further understood that terms (such as those defined in commonly used dictionaries) should be interpreted as having a meaning consistent with their meaning in the context of the relevant art and the present disclosure, and will not be interpreted as an idealized or overly formal meaning unless explicitly defined as such herein.
[0014] As used herein, "actinic rays" or "radiation" means, for example, the bright line spectrum of a mercury lamp, far ultraviolet rays represented by excimer lasers, extreme ultraviolet rays (EUV light), X-rays, particle rays (such as electron beams and ion beams), etc. In addition, in the present invention, "light" means actinic rays or radiation. Krypton fluoride laser (KrF laser) is a specific type of excimer laser, sometimes called an excimer laser. "Excimer" is an abbreviation for "excimer dimer", and "excimer" is an abbreviation for "excimer complex". Excimer lasers use a mixture of rare gases (argon, krypton or xenon) and halogen gases (fluorine or chlorine), which emit coherent stimulated radiation (laser) in the ultraviolet range under suitable electrical stimulation and high voltage conditions. In addition, unless otherwise specified, "exposure" in this specification includes not only exposure by mercury lamps, far ultraviolet rays represented by excimer lasers, X-rays, extreme ultraviolet rays (EUV light), etc., but also writing with particle rays (such as electron beams and ion beams).
[0015] As used herein, the term "hydrocarbon" refers to an organic compound or group having at least one carbon atom and at least one hydrogen atom; "alkyl" refers to a straight or branched saturated hydrocarbon group having a specified number of carbon atoms and having a valence of 1; "alkylene" refers to an alkyl group having a valence of 2; "hydroxyalkyl" refers to an alkyl group substituted with at least one hydroxyl group (-OH); "alkoxy" refers to "alkyl-O-"; "carboxyl" and "carboxylic acid group" refer to groups having the formula "-C(O)-OH"; "cycloalkyl" refers to a monovalent group having one or more saturated rings in which all ring members are carbon; "cycloalkylene" refers to a cycloalkyl group having a valence of 2; "alkenyl" refers to a straight or branched monovalent hydrocarbon group having at least one carbon-carbon double bond; "alkenyloxy" refers to "alkenyl-O-"; "alkenylene" refers to an alkenyl group having a valence of 2; "cycloalkenyl" refers to a cycloalkyl group having at least three carbon atoms, A non-aromatic cyclic divalent hydrocarbon group having at least one carbon-carbon double bond; "alkynyl" refers to a monovalent hydrocarbon group having at least one carbon-carbon triple bond; the term "aromatic group" refers to a monocyclic or polycyclic aromatic ring system that satisfies Huckel's rule (4n+2π electrons) and contains carbon atoms in the ring; the term "heteroaromatic group" refers to an aromatic group containing one or more heteroatoms (e.g., 1-4 heteroatoms) selected from N, O and S replacing carbon atoms in the ring; "aryl" refers to a monovalent monocyclic or polycyclic aromatic ring system in which each ring member is carbon and may include groups having an aromatic ring fused to at least one cycloalkyl or heterocycloalkyl ring; "arylene" refers to an aryl group having a valence of 2; "alkylaryl" refers to an aryl group that has been substituted by an alkyl group; "arylalkyl" refers to an alkyl group that has been substituted by an aryl group; "aryloxy" refers to "aryl-O-"; and "arylthio" refers to "aryl-S-".
[0016] The prefix "hetero" means that the compound or group contains at least one member (e.g., 1, 2, 3, or 4 or more heteroatoms) as a heteroatom replacing a carbon atom, wherein the one or more heteroatoms are each independently N, O, S, Si, or P; "heteroatom-containing group" refers to a substituted group containing at least one heteroatom; "heteroalkyl" refers to an alkyl group having at least one heteroatom replacing a carbon; "heterocycloalkyl" refers to a cycloalkyl group having 1-4 heteroatoms as ring members replacing a carbon; "heterocycloalkylene" refers to a cycloalkyl group having 1-4 heteroatoms as ring members replacing a carbon; 2; "heteroaryl" refers to an aromatic 4-8 membered monocyclic, 8-12 membered bicyclic, or 11-14 membered tricyclic ring system having 1-4 heteroatoms (if monocyclic), 1-6 heteroatoms (if bicyclic), or 1-9 heteroatoms (if tricyclic), each of which is independently selected from N, O, S, Si, or P (e.g., carbon atoms and 1-3, 1-6, or 1-9 heteroatoms of N, O, or S, respectively, if monocyclic, bicyclic, or tricyclic). Examples of heteroaryl groups include pyridyl, furanyl (furyl or furanyl), imidazolyl, benzimidazolyl, pyrimidinyl, thiophenyl or thienyl, quinolinyl, indolyl, thiazolyl, and the like; and "heteroarylene" refers to a heteroaryl group having a valence of 2.
[0017] The term "halogen" means a monovalent substituent of fluorine (fluorine, fluoro), chlorine (chlorine, chloro), bromine (bromine, bromo), or iodine (iodine, iodo). The prefix "halo" means a group containing one or more of fluorine, chlorine, bromine, or iodine substituents replacing a hydrogen atom. There may be a combination of halides (e.g., bromine and fluorine) or only fluorine groups. For example, the term "haloalkyl" refers to an alkyl group substituted with one or more halogens. As used herein, a "substituted C 1-8 "Haloalkyl" refers to a C 1-8 An alkyl group is further substituted with one or more other substituent groups that are not halogen. It should be understood that substitution of a group with a halogen atom should not be considered a heteroatom-containing group because the halogen atom is not replacing a carbon atom.
[0018] Unless otherwise expressly provided, each of the aforementioned substituent groups can be optionally substituted. The term "optionally substituted" refers to being substituted or unsubstituted. "Substituted" means that at least one hydrogen atom of a chemical structure or group is replaced by another terminal substituent group that is typically monovalent, provided that the normal valence of the specified atom is not exceeded. When the substituent is an oxo (i.e., O), then the two geminal hydrogen atoms on the carbon atom are replaced by terminal oxo groups. Further note that the oxo group is bonded to the carbon via a double bond to form a carbonyl (C=O), wherein the carbonyl group is represented herein as -C(O)-. Combinations of substituents or variables are permissible. Exemplary substituents that may be present in a "substituted" position include, but are not limited to, nitro (-NO2), cyano (-CN), hydroxyl (-OH), oxo (O), amino (-NH2), mono- or di-(C 1-6 ) alkylamino, alkanoyl (such as C 2-6 Alkanoyl groups, such as acyl), formyl (-C(O)H), carboxylic acids or their alkali metal or ammonium salts; esters (including acrylates, methacrylates and lactones) such as C 2-6 Alkyl esters (-C(O)O-alkyl or -OC(O)-alkyl) and C 7-13 Aryl esters (-C(O)O-aryl or -OC(O)-aryl); amides (-C(O)NR2, where R is hydrogen or C 1-6 alkyl), carboxamido (-CH2C(O)NR2, where R is hydrogen or C 1-6 alkyl), halogen, mercapto (-SH), C 1-6 Alkylthio (-S-alkyl), thiocyano (-SCN), C 1-6 Alkyl, C 2-6 Alkenyl, C 2-6 Alkynyl, C 1-6 Haloalkyl, C 1-9 Alkoxy, C 1-6 Halogenated alkoxy, C 3-12 Cycloalkyl, C 5-18 Cycloalkenyl, C 2-18 Heterocycloalkenyl, C 6-12 Aryl (e.g., phenyl, biphenyl, naphthyl, etc., each ring is substituted or unsubstituted aromatic), C having 1 to 3 separate or condensed rings and 6 to 18 ring carbon atoms 7-19 Arylalkyl, arylalkoxy having 1 to 3 separate or fused rings and 6 to 18 ring carbon atoms, C 7-12 Alkyl aryl, C 3-12 Heterocycloalkyl, C 3-12 Heteroaryl, C 1-6 Alkylsulfonyl (-S(O)2-alkyl), C 6-12Arylsulfonyl (-S(O)2-aryl), or tosyl (CH3C6H4SO2-).
[0019] As used herein, when no definition is otherwise provided, "divalent linking group" and "linking group" refer to -O-, -S-, -Te-, -Se-, -C(O)-, -C(O)O-, -N(R')-, -C(O)N(R')-, -S(O)-, -S(O)2-, -C(S)-, -C(Te)-, -C(Se)-, substituted or unsubstituted C 1-30 Alkylene, substituted or unsubstituted C 3-30 Cycloalkylene, substituted or unsubstituted C 3-30 Heterocycloalkylene, substituted or unsubstituted C 6-30 Arylene, substituted or unsubstituted C 3-30 A heteroarylene group, or one or more groups in a combination thereof, wherein each R' is independently hydrogen, substituted or unsubstituted C 1-20 Alkyl, substituted or unsubstituted C 1-20 Heteroalkyl, substituted or unsubstituted C 6-30 Aryl, substituted or unsubstituted C 3-30 Typically, the divalent linking group includes -O-, -S-, -C(O)-, -C(O)O-, -N(R')-, -C(O)N(R')-, -S(O)-, -S(O)2-, substituted or unsubstituted C 1-30 Alkylene, substituted or unsubstituted C 3-30 Cycloalkylene, substituted or unsubstituted C 3-30 Heterocycloalkylene, substituted or unsubstituted C 6-30 Arylene, substituted or unsubstituted C 3-30 heteroarylene, or one or more of a combination thereof, wherein R' is hydrogen, substituted or unsubstituted C 1-20 Alkyl, substituted or unsubstituted C 1-20 Heteroalkyl, substituted or unsubstituted C 6-30 Aryl, substituted or unsubstituted C 3-30 More typically, the divalent linking group includes -O-, -C(O)-, -C(O)O-, -N(R')-, -C(O)N(R')-, substituted or unsubstituted C 1-10 Alkylene, substituted or unsubstituted C 3-10 Cycloalkylene, substituted or unsubstituted C 3-10 Heterocycloalkylene, substituted or unsubstituted C 6-10 Arylene, substituted or unsubstituted C 3-10 or at least one of a heteroarylene group, or a combination thereof, wherein R is hydrogen, substituted or unsubstituted C 1-10 Alkyl, substituted or unsubstituted C1-10 Heteroalkyl, substituted or unsubstituted C 6-10 Aryl, substituted or unsubstituted C 3-10 Heteroaryl.
[0020] As used herein, "acid-labile groups" refer to groups in which bonds are cracked by the action of an acid, optionally and typically with heat treatment, resulting in the formation of polar groups, such as carboxylic acid or alcohol groups. In some cases, acid-labile groups can be formed on polymers, and optionally and typically disconnected from polymers together with the portion of the bond connected to the cracking. In other systems, non-polymeric compounds may include acid-labile groups, which can be cracked by the action of an acid, resulting in the formation of polar groups, such as carboxylic acid or alcohol groups, on the cracked portion of the non-polymeric compound. Such acids are typically photogenerated acids in the case of bond cracking during post-exposure baking (PEB); however, embodiments are not limited thereto, and, for example, such acids may be thermally generated. Suitable acid-labile groups include, for example, tertiary alkyl ester groups, secondary or tertiary aryl ester groups, secondary or tertiary ester groups with a combination of alkyl groups and aryl groups, tertiary alkoxy groups, acetal groups, or ketal groups. Acid labile groups are also often referred to in the art as "acid cleavable groups," "acid cleavable protecting groups," "acid labile protecting groups," "acid leaving groups," "acid decomposable groups," and "acid sensitive groups."
[0021] The present invention relates to multi-block copolymers, which provide solutions for compositional variations in polymers for photoresist compositions. For example, when a polymer is prepared by free radical polymerization or made using a controlled radical dump and run method, it generally results in uniformity problems between polymer chains in the composition or inhomogeneities along the polymer backbone. In typical free radical copolymerization or controlled radical copolymerization (or other chain copolymerization techniques), comonomers are unevenly distributed along the polymer backbone or between different polymer chains due to their different incorporation rates. The present invention provides a multi-block copolymer, wherein the polymer chain is decomposed into several blocks, wherein two or more blocks can have the same specific repeat unit composition, and optionally the same composition gradient, so that the multi-block copolymer can provide a substantially uniform distribution of repeat units along the entire polymer backbone.
[0022] The use of multi-block structures allows the final polymer properties to be adjusted based on monomer selection and gradient. For example, the properties obtained in traditional copolymers are typically the average of the properties imparted by the resulting monomers incorporated, while block copolymers result in composite materials containing characteristic properties inherent to each parent polymer block segment. The gradient structure using multi-block structures allows each block segment to be adjusted and further simplifies the copolymer synthesis method. U.S. Patent No. 6,887,962 and Patent Application 2004 / 0180019 give examples of gradient copolymers made by controlled radical polymerization (CRP).
[0023] When controlled radical polymerization (CRP) technology is used to synthesize copolymer segments, it is called a gradient copolymer. This type of copolymer is different from the copolymer obtained by traditional free radical methods, and the copolymer characteristics will depend on the monomer composition, the control agent used and the polymerization conditions. For example, when a monomer mixture is polymerized by traditional free radical polymerization, a statistical copolymer is produced. The polymer made at each moment during the polymerization is different in composition. In addition, due to the constant generation of free radicals and the changing monomer ratios during the entire reaction process, the composition between different polymer chains will be uneven. During CRP, the chain remains active throughout the polymerization process, so the composition between different polymer chains is uniform, but each chain will be gradient in composition. Therefore, in a two-monomer system in which one monomer reacts faster than another monomer, the distribution or "profile" of the monomer units will make a monomer unit have a higher concentration at one end of the block.
[0024] A block copolymer is provided, comprising: a first block comprising two or more structurally different repeating units; and a second block comprising two or more structurally different repeating units. The repeating units of the first block comprise an acid-labile group, a lactone group, a salt group, or a hydroxyaryl group; and the repeating units of the second block comprise an acid-labile group, a lactone group, a salt group, or a hydroxyaryl group, wherein the two or more structurally different repeating units of the first block are the same as the two or more structurally different repeating units of the second block. For example, the first block and the second block may each comprise two structurally different repeating units, three structurally different repeating units, or four or more structurally different repeating units, provided that the first block and the second block have the same structurally different repeating units.
[0025] It should be noted that the block copolymer may optionally further include other blocks (i.e., the third, fourth, fifth, etc. blocks) that may be identical or different from the first block and the second block as described herein. In some embodiments, the block copolymer may further include a block that does not have a structurally different repeating unit identical to the first block and the second block. For example, the block copolymer may include a third block, wherein the third block includes a repeating unit that may be different from the repeating unit of the first block and the second block. In other embodiments, the block copolymer may include a third block and a fourth block, wherein the third block includes a repeating unit that may be different from the repeating unit of the first block and the second block, and the fourth block may include a repeating unit different from the repeating unit of the first block, the second block, and the third block. The additional blocks of the block copolymer may each include a single repeating unit, or the additional blocks of the block copolymer may each include two or more structurally different repeating units. In some embodiments, when the block copolymer comprises additional blocks, the additional blocks can each comprise two or more structurally different repeating units, wherein the two or more structurally different repeating units can be different or the same between each additional block and relative to the first and second blocks.
[0026] In some embodiments, each block of the block copolymer can have the same two or more structurally different repeating units. In other words, in some embodiments, the block copolymer does not contain additional blocks or multiple blocks having polymerized units different from the repeating units in the first block and the second block.
[0027] The two or more structurally different repeating units of the first block and the two or more structurally different repeating units of the second block can be present in the first block and the second block in any suitable ratio, and for example, the molar ratio of the two or more structurally different repeating units of the first block can be the same or different than the molar ratio of the two or more structurally different repeating units of the second block. For example, a block copolymer can have a first block of repeating units A and B and a second block of repeating units A and B, wherein the ratio of repeating units A to repeating units B in the first block can be the same or different than the ratio of repeating units A to repeating units B in the second block. When the block copolymer comprises one or more additional blocks in addition to the first block and the second block, each additional block can independently have any suitable ratio of structurally different repeating units.
[0028] In some embodiments, two or more structurally different repeating units of the first block and two or more structurally different repeating units of the second block may be present in the first block and the second block at substantially the same ratio, and each block has the same structural unit gradient direction from the first end of the block to the second end. For example, two or more structurally different repeating units of the first block and two or more structurally different repeating units of the second block may be present in the first block and the second block in substantially the same molar ratio based on the total molar number of repeating units in the corresponding first block and the second block. As used herein, the term "structural unit gradient direction" may refer to a gradient based on the molar ratio of repeating units. In some embodiments, each block of a block copolymer may have the same two or more structurally different repeating units, wherein the two or more structurally different repeating units of each block may be present in substantially the same ratio, and each block has the same structural unit gradient direction from the first end of the block to the second end.
[0029] As noted above, the repeating units of the first block and the second block of the block copolymer include an acid-labile group, a lactone group, a salt group, or a hydroxyaryl group. For example, in some embodiments, the first block and the second block may each include a repeating unit containing an acid-labile group. In some embodiments, the first block and the second block may each include a repeating unit containing a lactone group or a salt group. For example, in some embodiments, the first block and the second block of the block copolymer may each include a first repeating unit containing an acid-labile group and a second repeating unit containing a lactone group or a salt group.
[0030] In certain embodiments, the first block and the second block of block copolymer can each include the first repeating unit containing acid-labile groups and the second repeating unit containing lactone groups.In other embodiments, the first block and the second block of block copolymer can each include the first repeating unit containing acid-labile groups, the second repeating unit containing the first lactone groups and the third repeating unit containing the second lactone groups, wherein the first lactone groups and the second lactone groups are different.In other embodiments, the first block and the second block of block copolymer can each include the first repeating unit containing the first acid-labile groups, the second repeating unit containing the second acid-labile groups and the third repeating unit containing lactone groups, wherein the first acid-labile groups and the second acid-labile groups are different.
[0031] Suitable acid-labile groups include, for example, tertiary alkyl ester groups, secondary or tertiary aryl ester groups, secondary or tertiary ester groups, tertiary alkoxy groups, acetal groups, ketal groups, tertiary carbonate groups and tertiary carbamate groups with a combination of an alkyl group and an aryl group. Typically, acid-labile groups can be acetal groups, ketal groups, tertiary carbonate groups, tertiary carbamate groups or tertiary ester groups. As used herein, "tertiary carbamate groups" include tertiary carbamate groups with an alkyl group, tertiary carbamate groups with an aryl group and tertiary carbamate groups with a combination of an alkyl group and an aryl group. As used herein, "tertiary carbonate groups" include tertiary carbonate groups with an alkyl group, tertiary carbonate groups with an aryl group and tertiary carbonate groups with a combination of an alkyl group and an aryl group. Preferably, acid-labile groups include tertiary ester groups.
[0032] The repeating units of the block copolymer may contain an acid-labile group represented by one or more of formulae (1) to (5):
[0033] In equations (1) to (3), each R a are independently hydrogen, fluorine, cyano, substituted or unsubstituted C 1-10 Alkyl, substituted or unsubstituted C 1-10 Preferably, R a is hydrogen, fluorine, or substituted or unsubstituted C 1-5 The alkyl group is typically methyl.
[0034] In formula (1), L 1 is a divalent linking group. For example, L 1 It can be a divalent linking group comprising at least one carbon atom, at least one heteroatom, or a combination thereof. 1 Can contain 1 to 10 carbon atoms and at least one heteroatom. In one or more embodiments, L 1 It can be -OCH2-, -OCH2CH2O- or -N(R c )-, where R c is hydrogen, substituted or unsubstituted C 1-10 Alkyl, substituted or unsubstituted C 1-10 Heteroalkyl, substituted or unsubstituted C 6-10 Aryl, substituted or unsubstituted C 3-10 Heteroaryl.
[0035] In formulas (1), (2) and (4), R 1 To R 3 can each independently be hydrogen, substituted or unsubstituted C 1-20 Alkyl, substituted or unsubstituted C3-20 Cycloalkyl, substituted or unsubstituted C 1-20 Heterocycloalkyl, substituted or unsubstituted C 2-20 Alkenyl, substituted or unsubstituted C 3-20 Cycloalkenyl, substituted or unsubstituted C 3-20 Heterocycloalkenyl, substituted or unsubstituted C 6-20 Aryl, substituted or unsubstituted C 2-20 Heteroaryl; provided that R 1 To R 3 Only one of them may be hydrogen, provided that when R 1 To R 3 When one of the 1 To R 3 The other one or two of them are substituted or unsubstituted C 6-20 Aryl or substituted or unsubstituted C 4-20 Preferably, R 1 To R 3 are each independently substituted or unsubstituted C 1-6 Alkyl or substituted or unsubstituted C 3-10 Cycloalkyl.
[0036] In formulas (1), (2) and (4), R 1 To R 3 Any two of together optionally form a ring, and R 1 To R 3 Each of these may optionally contain as part of their structure one or more selected from -O-, -C(O)-, -N(R c )-, -S-, -S(O)-, or -S(O)2-, wherein R c Can be hydrogen, straight chain or branched C 1-20 Alkyl, monocyclic or polycyclic C 3-20 Cycloalkyl, or monocyclic or polycyclic C 1-20 Heterocycloalkyl. For example, R 1 To R 3 Any one or more of may independently be of the formula -CH2C(=O)CH (3-n) Y n wherein each Y is independently substituted or unsubstituted C 1-30 heterocycloalkyl, and n is 1 or 2. For example, each Y can independently be a a1 )(C a2 )O-substituted or unsubstituted C 1-30 Heterocycloalkyl, wherein C a1 and C a2 are each independently hydrogen or substituted or unsubstituted C 1-10Alkyl, and wherein C a1 and C a2 Together they optionally form a ring.
[0037] In equations (3) and (5), R 4 and R 5 can each independently be hydrogen, substituted or unsubstituted C 1-20 Alkyl, substituted or unsubstituted C 3-20 Cycloalkyl, substituted or unsubstituted C 1-20 Heterocycloalkyl, substituted or unsubstituted C 6-20 Aryl, substituted or unsubstituted C 2-20 heteroaryl; and R 6 Can be substituted or unsubstituted C 1-20 Alkyl, substituted or unsubstituted C 3-20 Cycloalkyl, substituted or unsubstituted C 1-30 Heterocycloalkyl. 4 or R 5 One of the 6 Together they can form a heterocyclic ring. Preferably, R 4 and R 5 can each independently be hydrogen, substituted or unsubstituted C 1-20 Alkyl, substituted or unsubstituted C 3-20 Cycloalkyl, substituted or unsubstituted C 1-20 Heterocycloalkyl.
[0038] In equations (4) and (5), L 2 and L 3 Each is independently a single bond or a divalent linking group. Preferably, L 2 and L 3 are each independently substituted or unsubstituted C 6-30 Arylene or substituted or unsubstituted C 3-30 For example, in some embodiments, L 3 It contains no (meth)acrylate groups as part of its structure.
[0039] In formulas (4) and (5), each of n1 and n2 can be independently 0 or 1. It should be understood that when n1 or n2 is 0, the corresponding L 2 or L 3 The groups are directly attached to the corresponding oxygen atoms.
[0040] Non-limiting examples of repeating units having an acid labile group include the following: Where R d is hydrogen, halogen, substituted or unsubstituted C 1-6 Alkyl, substituted or unsubstituted C 3-6 Cycloalkyl.
[0041] The repeating units containing acid labile groups in the blocks of the block copolymers can typically be present in an amount of 10 mole percent (mol%) to 90 mol%, more typically 10 mol% to 65 mol%, and more typically 15 mol% to 60 mol%, based on the total repeating units of the block. The repeating units containing acid labile groups can typically be present in the block copolymer in an amount of 10 mol% to 90 mol%, more typically 10 mol% to 65 mol%, and more typically 25 mol% to 60 mol%, based on the total repeating units of the block copolymer.
[0042] The repeating units of the block copolymer may contain a lactone group. For example, the repeating units of the block copolymer may contain a lactone group represented by formula (6):
[0043] In formula (6), R a It may be hydrogen, fluorine, cyano, or substituted or unsubstituted C 1-10 Preferably, R a It may be hydrogen, fluorine, or substituted or unsubstituted C 1-5 Alkyl is typically hydrogen or methyl.
[0044] In formula (6), L 4 It can be a single bond or one or more divalent linking groups. 4 It can be -O-, -C(O)-, -C(O)O-, -N(R c )-、-C(O)N(R c )-, substituted or unsubstituted C 1-10 Alkylene, substituted or unsubstituted C 3-10 Cycloalkylene, substituted or unsubstituted C 3-10 Heterocycloalkylene, substituted or unsubstituted C 6-10 Arylene, substituted or unsubstituted C 3-10 heteroarylene, or a combination thereof, wherein R c It can be hydrogen, substituted or unsubstituted C 1-30 Alkyl, substituted or unsubstituted C 1-30 Heteroalkyl, substituted or unsubstituted C 3-30 Cycloalkyl, substituted or unsubstituted C 1-30 Heterocycloalkyl, substituted or unsubstituted C 2-30 Alkenyl, substituted or unsubstituted C2-30 Alkynyl, substituted or unsubstituted C 6-30 Aryl, substituted or unsubstituted C 7-30 Arylalkyl, substituted or unsubstituted C 7-30 Alkyl aryl, substituted or unsubstituted C 2-30 Heteroaryl, substituted or unsubstituted C 3-30 Heteroarylalkyl, or substituted or unsubstituted C 3-30 In some aspects, L 4 It may be a single bond, or one or more groups selected from: -C(O)O-, substituted or unsubstituted C 1-10 Alkylene, substituted or unsubstituted C 3-10 Cycloalkylene, substituted or unsubstituted C 3-10 Heterocycloalkylene, substituted or unsubstituted C 6-10 Arylene, substituted or unsubstituted C 3-10 a heteroarylene group, or a combination thereof.
[0045] In formula (6), R 7 It can be a monocyclic, polycyclic, or fused polycyclic C 4-20 Contains lactone group.
[0046] Non-limiting examples of lactone-containing repeating units having formula (6) may include: Where R d It may be hydrogen, fluorine, cyano, or substituted or unsubstituted C 1-10 Preferably, R d It may be hydrogen, fluorine, or substituted or unsubstituted C 1-5 The alkyl group is typically methyl.
[0047] The repeating units containing lactone groups in the blocks of the block copolymers are typically present in an amount of 20 mol% to 90 mol%, more typically 25 mol% to 75 mol%, and more typically 30 mol% to 70 mol%, based on the total repeating units of the block. The repeating units containing lactone groups are typically present in the block copolymers in an amount of 20 mol% to 90 mol%, more typically 25 mol% to 75 mol%, and more typically 30 mol% to 70 mol%, based on the total repeating units of the block copolymer.
[0048] The repeating unit of the block copolymer may contain a salt group. As used herein, a "salt group" refers to a portion having a positive charge and a negative charge, such as a portion having a positively charged or negatively charged side chain bonded to the main chain of the block copolymer. The repeating unit of the block copolymer containing a salt group may contain a photoacid generator (PAG) group or a photodecomposable quencher (PDQ) group. For example, the repeating unit of the block copolymer may contain a salt group represented by formula (7a) or (7b):
[0049] In equations (7a) and (7b), each R m It may be hydrogen, fluorine, cyano, or substituted or unsubstituted C 1-10 Preferably, R m is hydrogen, fluorine, or substituted or unsubstituted C 1-5 The alkyl group is typically methyl.
[0050] In equations (7a) and (7b), Q 1 and Q 2 Can be each independently a single bond or a divalent linking group. Preferably, Q 1 and Q 2 Each may independently contain 1 to 10 carbon atoms and at least one heteroatom, more preferably -C(O)-O-.
[0051] In equations (7a) and (7b), A 1 and A 2 may be independently one or more of the following: substituted or unsubstituted C 1-30 Alkylene, substituted or unsubstituted C 3-30 Cycloalkylene, substituted or unsubstituted C 2-30 Heterocycloalkylene, substituted or unsubstituted C 6-30 Arylene, or substituted or unsubstituted C 3-30 In some embodiments, A 1 and A 2 may each independently be an optionally substituted divalent C 1-30 Perfluoroalkylene groups.
[0052] In formula (7a), Z - is bonded to A 1 The anionic portion of Z, its conjugate acid typically has a pKa of -15 to 10. - It may be a sulfonate, carboxylate, sulfonamide anion, sulfonimide anion, or methide anion.
[0053] In formula (7a), G + is an organic cation as defined herein. In some embodiments, G+ is an iodonium cation substituted with two alkyl groups, two aryl groups, or a combination of an alkyl group and an aryl group; or is a sulfonium cation substituted with three alkyl groups, three aryl groups, or a combination of an alkyl group and an aryl group.
[0054] In formula (7b), Z - is an anionic compound as defined herein, the conjugate acid of which typically has a pKa of -15 to 10. - It may be a sulfonate, carboxylate, an anion of a sulfonamide, an anion of a sulfonimide, or a methide anion species. For example, Z- may be as defined herein for anion A-.
[0055] In formula (7b), G + is bonded to A 2 For example, G + An iodonium cation substituted with two alkyl groups, two aryl groups, or a combination of alkyl groups and aryl groups; or a sulfonium cation substituted with three alkyl groups, three aryl groups, or a combination of alkyl groups and aryl groups may be included.
[0056] In still other embodiments, when the block copolymer comprises repeating units having salt groups, the block copolymer may comprise zwitterionic substances. For example, a block of the block copolymer may comprise repeating units having salt groups of formula (7c): In formula (7c), each R m and are independently as defined for formulae (7a) and (7b).
[0057] In formula (7c), Q 1 , A 1 and Z - is as defined in equation (7a), and Q 2 , A 2 and G + is defined as in formula (7b).
[0058] Exemplary repeating units having formula (7a) include the following: Where G is an organic cation and each R d are independently defined as in formula (7a).
[0059] Exemplary repeating units having formula (7b) include the following: Where Z- is an anionic group as defined herein, and each R d and are independently as defined for formula (7b).
[0060] The repeating units containing salt in the blocks of the block copolymers are typically present in an amount of 1 mol% to 35 mol%, typically 1 mol% to 25 mol%, more typically 2 mol% to 15 mol%, based on the total repeating units of the block. The repeating units containing salt can be present in the block copolymer in an amount of 1 mol% to 35 mol%, typically 1 mol% to 25 mol%, more typically 2 mol% to 15 mol%, based on the total repeating units of the block copolymer.
[0061] The repeating units of the block copolymer may contain a hydroxyaryl group. Exemplary hydroxyaryl groups include phenol groups or naphthol groups. For example, the repeating units of the block copolymer may contain a hydroxyaryl group represented by formula (8):
[0062] In formula (8), R a It may be hydrogen, fluorine, cyano, or substituted or unsubstituted C 1-10 Preferably, R a It may be hydrogen, fluorine, or substituted or unsubstituted C 1-5 Alkyl is typically hydrogen or methyl.
[0063] In formula (8), L 5 It can be a single bond or one or more divalent linking groups. 5 It can be -O-, -C(O)-, -C(O)O-, -N(R c )-、-C(O)N(R c )-, substituted or unsubstituted C 1-10 Alkylene, substituted or unsubstituted C 3-10 Cycloalkylene, substituted or unsubstituted C 3-10 Heterocycloalkylene, substituted or unsubstituted C 6-10 Arylene, substituted or unsubstituted C 3-10 heteroarylene, or a combination thereof, wherein R c It can be hydrogen, substituted or unsubstituted C 1-30 Alkyl, substituted or unsubstituted C 1-30 Heteroalkyl, substituted or unsubstituted C 3-30 Cycloalkyl, substituted or unsubstituted C 1-30 Heterocycloalkyl, substituted or unsubstituted C 2-30 Alkenyl, substituted or unsubstituted C 2-30 Alkynyl, substituted or unsubstituted C 6-30 Aryl, substituted or unsubstituted C7-30 Arylalkyl, substituted or unsubstituted C 7-30 Alkyl aryl, substituted or unsubstituted C 2-30 Heteroaryl, substituted or unsubstituted C 3-30 Heteroarylalkyl, or substituted or unsubstituted C 3-30 In some aspects, L 5 It may be a single bond, or one or more groups selected from: -C(O)O-, substituted or unsubstituted C 1-10 Alkylene, substituted or unsubstituted C 3-10 Cycloalkylene, substituted or unsubstituted C 3-10 Heterocycloalkylene, substituted or unsubstituted C 6-10 Arylene, substituted or unsubstituted C 3-10 a heteroarylene group, or a combination thereof.
[0064] In formula (8), Ar 1 Can be substituted C 5-60 An aromatic group, which optionally contains one or more aromatic ring heteroatoms selected from N, O, S, or a combination thereof, wherein the aromatic group may be a monocyclic, non-fused polycyclic, or fused polycyclic. 5-60 When the aromatic group is polycyclic, the rings or ring groups may be fused (such as naphthyl, etc.), non-fused, or a combination thereof. 5-60 When the aromatic group is non-fused, the ring or ring groups may be directly connected (such as biaryl, biphenyl, etc.) or may be bridged by heteroatoms (such as triphenylamino or diphenylene ether). 5-60 Aromatic groups may include a combination of fused rings and directly linked rings (eg, binaphthyl, etc.).
[0065] In formula (8), y may be an integer of 1 to 12, preferably 1 to 6, and typically 1 to 3.
[0066] In formula (8), each R x may independently be hydrogen or methyl, provided that at least one R x It's hydrogen.
[0067] Non-limiting examples of such repeating units having formula (8) may include: Where R d It may be hydrogen, fluorine, cyano, or substituted or unsubstituted C 1-10 Preferably, R d It may be hydrogen, fluorine, or substituted or unsubstituted C 1-5 The alkyl group is typically methyl.
[0068] The repeating units containing hydroxyaryl groups in the blocks of the block copolymers can typically be present in an amount of 10 mole percent (mol%) to 90 mol%, more typically 15 mol% to 75 mol%, and more typically 25 mol% to 70 mol%, based on the total repeating units of the block. The repeating units containing hydroxyaryl groups can typically be present in the block copolymer in an amount of 10 mol% to 90 mol%, more typically 15 mol% to 75 mol%, and more typically 25 mol% to 70 mol%, based on the total repeating units of the block copolymer.
[0069] In some aspects, the block of the block copolymer may further optionally include one or more additional repeating units. Additional repeating units may be, for example, one or more additional units for the purpose of regulating the characteristics of the block copolymer. Exemplary additional repeating units may include those derived from one or more of (meth) acrylates, vinyl aromatic compounds, vinyl ethers, vinyl ketones, and / or vinyl ester monomers. The one or more additional repeating units (if present in the block of the block copolymer) may be used in an amount of up to 80mol%, typically 3mol% to 50mol% based on the total repeating units of the block. The one or more additional repeating units (if present) may be used in an amount of up to 80mol%, typically 3mol% to 50mol% based on the total repeating units of the block copolymer.
[0070] In certain embodiments, the block copolymer may include repeating units containing polar groups. Exemplary polar groups include sultone groups, sulfonamide groups, hydroxyalkyl groups, hydroxycycloalkyl groups, or combinations thereof. It should be understood that some groups, such as lactone groups or hydroxyaryl groups, may be considered as polar groups, however, these groups are different from polar groups as used herein.
[0071] The repeating unit of the block copolymer may contain a polar group represented by formula (9)
[0072] In formula (9), R a It may be hydrogen, fluorine, cyano, or substituted or unsubstituted C 1-10 Preferably, R a It may be hydrogen, fluorine, or substituted or unsubstituted C 1-5 Alkyl is typically hydrogen or methyl.
[0073] In formula (9), L 6 It can be a single bond or one or more divalent linking groups. 6 It can be -O-, -C(O)-, -C(O)O-, -N(R c)-、-C(O)N(R c )-, substituted or unsubstituted C 1-10 Alkylene, substituted or unsubstituted C 3-10 Cycloalkylene, substituted or unsubstituted C 3-10 Heterocycloalkylene, substituted or unsubstituted C 6-10 Arylene, substituted or unsubstituted C 3-10 heteroarylene, or a combination thereof, wherein R c It can be hydrogen, substituted or unsubstituted C 1-30 Alkyl, substituted or unsubstituted C 1-30 Heteroalkyl, substituted or unsubstituted C 3-30 Cycloalkyl, substituted or unsubstituted C 1-30 Heterocycloalkyl, substituted or unsubstituted C 2-30 Alkenyl, substituted or unsubstituted C 2-30 Alkynyl, substituted or unsubstituted C 6-30 Aryl, substituted or unsubstituted C 7-30 Arylalkyl, substituted or unsubstituted C 7-30 Alkyl aryl, substituted or unsubstituted C 2-30 Heteroaryl, substituted or unsubstituted C 3-30 Heteroarylalkyl, or substituted or unsubstituted C 3-30 In some aspects, L 6 It may be a single bond, or one or more groups selected from: -C(O)O-, substituted or unsubstituted C 1-10 Alkylene, substituted or unsubstituted C 3-10 Cycloalkylene, substituted or unsubstituted C 3-10 Heterocycloalkylene, substituted or unsubstituted C 6-10 Arylene, substituted or unsubstituted C 3-10 a heteroarylene group, or a combination thereof.
[0074] In formula (9), R 8 Can be substituted or unsubstituted C 1-100 or C 1-20 Alkyl, typically C 1-12 Alkyl; substituted or unsubstituted C 3-30 or C 3-20 Cycloalkyl; or substituted or unsubstituted poly(C 1-3 alkylene oxide). Substituted C 1-100 or C 1-20 Alkyl, substituted C 3-30 or C 3-20 Cycloalkyl, and substituted poly(C 1-3The alkylene oxide) is substituted with one or more of a sulfonamide group (e.g., -NHSO2CF3), a hydroxyl group (-OH), or a fluoroalcohol group (e.g., -C(CF3)2OH).
[0075] Non-limiting examples of repeating units having formula (9) may include: Where R g It may be hydrogen, fluorine, cyano, or substituted or unsubstituted C 1-10 Preferably, R g It may be hydrogen, fluorine, or substituted or unsubstituted C 1-5 Alkyl, typically methyl. 1 Can be F or C 1-4 Perfluoroalkyl.
[0076] In some embodiments, the block copolymer may include repeating units containing acid groups. Exemplary acid groups include carboxylic acid groups. The repeating units of the block copolymer may include acid groups represented by formula (10):
[0077] In formula (10), R a It may be hydrogen, fluorine, cyano, or substituted or unsubstituted C 1-10 Preferably, R a It may be hydrogen, fluorine, or substituted or unsubstituted C 1-5 Alkyl is typically hydrogen or methyl.
[0078] In formula (10), L 7 It can be a single bond or one or more of the following: substituted or unsubstituted C 1-30 Alkylene, substituted or unsubstituted C 3-30 Cycloalkylene, substituted or unsubstituted C 1-30 Heterocycloalkylene, substituted or unsubstituted C 6-30 Arylene, substituted or unsubstituted divalent C 7-30 Arylalkyl, substituted or unsubstituted C 1-30 Heteroarylene, or substituted or unsubstituted divalent C 3-30 heteroarylalkyl, or -C(O)-O-.
[0079] In formula (10), R 9 It may be -C(O)-OH.
[0080] Non-limiting examples of repeating units having formula (10) may include: Where R dIt may be hydrogen, fluorine, cyano, or substituted or unsubstituted C 1-10 Preferably, R d It may be hydrogen, fluorine, or substituted or unsubstituted C 1-5 The alkyl group is typically methyl.
[0081] The repeating units containing acid groups in the blocks of the block copolymers are typically present in an amount of 1 mol% to 20 mol%, more typically 5 mol% to 20 mol%, and more typically 5 mol% to 10 mol%, based on the total repeating units of the block. The repeating units containing hydroxyaryl groups are typically present in the block copolymer in an amount of 1 mol% to 20 mol%, more typically 5 mol% to 20 mol%, and more typically 5 mol% to 10 mol%, based on the total repeating units of the block copolymer.
[0082] Non-limiting exemplary first and second blocks of the block copolymers of the present invention include the following: wherein w1, w2, x1, x2, y1, y2, z1, and z2 each represent mol % of a repeating unit based on 100 mol % of the total repeating units in a block of the block copolymer.
[0083] In block copolymers, the average number of repeating units in each block can be 5 or more. Typically, the average number of polymerized units in each block can be 10 or more, or 20 or more, or 100 or more. For example, a triblock copolymer comprising three blocks can have 15 or more, or 30 or more, or 75 or more, or 150 or more total repeating units.
[0084] In block copolymers, the average number of blocks in the block copolymer may be 3 to 10. Typically, the block copolymer may have an average number of blocks of 3 to 5.
[0085] The weight average molecular weight (M w ) is typically 2,500 to 50,000 grams per mole (g / mol), preferably 2,500 to 30,000 g / mol, more preferably 2,500 to 20,000 g / mol, and still more preferably 2,500 to 15,000 g / mol. Dispersibility Index of Block Copolymers (It is M w With M n The ratio of M is typically 1.1 to 3, more typically 1.1 to 2, and preferably 1.1 to 1.7, 1.1 to 1.6, or 1.1 to 1.5 (M nis the number average molecular weight). Molecular weights were determined by gel permeation chromatography (GPC) using polystyrene standards.
[0086] A block copolymer is also provided, which comprises a plurality of block copolymers as described herein, wherein each of the plurality of block copolymers is different. That is, on the one hand, a block copolymer is provided, which is derived from a plurality of block copolymers as described herein, wherein each of the plurality of block copolymers is different. For example, this block copolymer may comprise a first segment of a first block copolymer derived from a repeating unit having a first gradient, and a second segment of a second block copolymer derived from a repeating unit having a second gradient, wherein the repeating unit of the first gradient is different from the repeating unit of the second gradient.
[0087] Another aspect provides a polymer comprising one or more block copolymers, wherein the block copolymer is bonded to another portion of the polymer. In other words, in some aspects, the block copolymers described herein can be bonded (eg, grafted) to another polymer using any suitable method.
[0088] Block copolymers can be prepared using any one or more suitable methods in the art. For example, one or more monomers corresponding to the polymerized units described herein can be combined or fed separately using one or more suitable solvents and initiators and polymerized in a reactor. For example, block copolymers can be obtained by polymerization of the corresponding monomers under any suitable conditions, such as by heating at an effective temperature, irradiating with actinic radiation at an effective wavelength, or a combination thereof.
[0089] Each monomer corresponding to the repeating unit described herein independently comprises a polymerizable group having a carbon-carbon unsaturated vinyl group and can typically be selected from substituted or unsubstituted C 2-20 The polymerizable groups of each monomer are independently substituted or unsubstituted C 2-20 Preferably, the polymerizable group of each monomer is independently a substituted or unsubstituted (meth) acrylic group, or a substituted or unsubstituted vinyl aromatic group.
[0090] Block copolymers can be prepared using living or controlled radical polymerization techniques, including reversible addition fragmentation chain transfer polymerization (RAFT), nitroxide-mediated polymerization (NMP), atom transfer radical polymerization (ATRP), etc. Unlike controlled radical polymerization, conventional radical polymerization is usually carried out at a relatively uncontrolled rate until one or more monomer reactants are exhausted. The average molecular weight can usually be controlled by controlling the initiator loading, monomer loading, initiation rate, termination rate, and propagation rate; however, due to the difficulty in accurately controlling when chain termination reactions may occur on any single large radical chain, conventional radical polymerization may result in a wide range of polymer chain lengths in the polymer molecule population, thereby producing highly polydispersed copolymers. When the side reactions that lead to polymer chain termination are eliminated or significantly reduced, controlled radical polymerization occurs, and the degree of polymerization is manipulated by controlling the balance of reversible transformations between active polymer chains in the active form of large radicals that propagate chain growth and inactive or dormant macromolecules that cannot propagate chain growth unless converted into active large radical forms. Thus, controlled free radical polymerization can produce block copolymers by free radical chain extension, where the molecular weight is easily controlled and with improved lower polydispersity.
[0091] The polymerization can use a chain transfer agent (CTA), including thiocarbonylthio compounds, such as dithioesters, thiocarbamates, xanthates, etc., to mediate polymerization via a reversible chain transfer process. In some embodiments, block copolymers can be produced by reacting one or more selected monomers with a dithioester chain transfer agent and an initiator to produce a block copolymer. In some embodiments, the initiator can be light.
[0092] Exemplary chain transfer agents (CTAs) for controlled free radical polymerization include thiocarbonylthio compounds such as 2-cyano-2-propyl benzodithioate, 4-cyano-4-(phenylthioformylthio)pentanoic acid, 2-cyano-2-propyl dodecyl trithiocarbonate, 4-cyano-4-[(dodecylsulfanylthiocarbonyl)sulfanyl]pentanoic acid, 2-(dodecylthioformylthio)-2-methylpropionic acid, cyanomethyl dodecyl trithiocarbonate, cyanomethyl methyl(phenyl)dithiocarbamate, bis(thiobenzoyl)disulfide, bis(dodecylsulfanyl-thiocarbonyl)disulfide, and the like.
[0093] Examples of initiators include azobis(isobutyronitrile) (AIBN), azobis(2-methylbutyronitrile), azobis(2,4-dimethylvaleronitrile), azobis(4-cyanovaleric acid). Examples of peroxides and peroxy initiators include hydrogen peroxide, sodium peroxide, potassium peroxide, tert-butyl hydroperoxide, cumene hydroperoxide, dilauroyl peroxide, tert-butyl peroxyneodecanoate, dibenzoyl peroxide, cumene peroxide, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxydiethylacetate, and tert-butyl peroxybenzoate. Examples of additional initiators include ammonium persulfate and / or alkali metal persulfates, sodium perborate, perphosphoric acid and its salts, potassium permanganate, and ammonium or alkali metal salts of peroxodisulfuric acid, examples being alkali metal or ammonium salts of peroxodisulfuric acid, diacetyl peroxide, dibenzoyl peroxide, succinyl peroxide, di-tert-butyl peroxide, tert-butyl perbenzoate, tert-butyl perpivalate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl permaleate, cumene hydroperoxide, diisopropyl peroxydicarbamate, bis(o-toluoyl)peroxide, didecanoyl peroxide, dioctanoyl peroxide, dilauroyl peroxide, tert-butyl perisobutyrate, tert-butyl peracetate, di-tert-amyl peroxide, tert-butyl hydroperoxide, azobisisobutyronitrile, 2,2′-azobis(2-amidino-propane) dihydrochloride or 2,2′-azobis(2-methylbutyronitrile). Mixtures of these initiators are also suitable. As initiators, reduction / oxidation (i.e., redox) initiator systems can also be used. Redox initiator systems are composed of at least one reducing agent, which is usually inorganic, and an organic or inorganic oxidant. The oxidizing component includes, for example, the polymerization initiator specified above. The reducing component includes, for example, an alkali metal salt of sulfurous acid, such as sodium sulfite, sodium bisulfite, an alkali metal salt of disulfurous acid, such as sodium pyrosulfite, a bisulfite addition compound of aliphatic aldehydes and ketones, such as acetone bisulfite, or a reducing agent, such as hydroxymethanesulfinic acid and its salts, or ascorbic acid. Redox initiator systems can be used together with soluble metal compounds, the metal components of which can exist in multiple valence states. Typical redox initiator systems are, for example, ascorbic acid / iron sulfate (II) / sodium peroxodisulfate, tert-butyl hydroperoxide / sodium pyrosulfite, tert-butyl hydroperoxide / sodium hydroxymethanesulfinate. Individual components, such as the reducing component, may also be mixtures, an example being a mixture of the sodium salt of hydroxymethanesulfinic acid and sodium metabisulfite.
[0094] Nitroxide-mediated polymerization or NMP using stable nitroxide free radicals or alkoxyamines as initiators can also be used to prepare block copolymers. Examples of suitable initiators for NMP include N-tert-butyl-N-(2-methyl-1-phenylpropyl)-O-(1-phenylethyl)hydroxylamine, N-tert-butyl-O-[1-[4-(chloromethyl)phenyl]ethyl]-N-(2-methyl-1-phenylpropyl)hydroxylamine, 2,2,5-trimethyl-4-phenyl-3-azahexane-3-nitroxide, 2,2,6,6-tetramethyl-1-piperidinyloxy (TEMPO), and the like.
[0095] Block copolymers can also be prepared using atom transfer radical polymerization or ATRP. Suitable initiators for ATRP include α-tert-butyl bromoisobutyrate, α-bromoisobutyryl bromide, 2-bromoisobutyric acid dodecyl esters, α-ethyl bromoisobutyrate, α-methyl bromoisobutyrate, 2-octadecyl bromoisobutyrate, etc. Suitable catalysts for ATRP include copper chloride (I), copper chloride (II), copper bromide (I), copper bromide (II), copper iodide (I), etc. Suitable ligands for ATRP include tris (2-pyridylmethyl) amine, tris [2- (dimethylamino) ethyl] amine, 4,4'-dinonyl-2,2'-bipyridine, N,N,N',N",N"-pentamethyldiethylenetriamine, etc.
[0096] The initiator may be used in a molar ratio of 0.05 to 2 relative to the chain transfer agent. In an exemplary embodiment, the initiator may be used in a molar ratio of 0.07 to 1 relative to the chain transfer agent.
[0097] The amount of initiator is typically at least 0.01 wt % or 0.05 wt % or 0.01 wt % to 10 wt %, or 5 wt % or 3 wt %, based on all monomers to be polymerized.
[0098] The polymerization reaction for preparing the block copolymer can be carried out in any suitable solvent, although the polymerization can also be carried out in the absence of a solvent. Exemplary polymerization solvents include ethers, cyclic ethers, C 5-10 Alkanes, which can be 1 to 3 C 1-4 Alkyl substituted C 5-8 Cycloalkanes, aromatic hydrocarbon solvents, halogenated hydrocarbon solvents, acetonitrile, dimethylformamide, ethylene carbonate, propylene carbonate, dimethyl sulfoxide, dimethyl sulfone, water, mixtures of such solvents, supercritical solvents (such as CO2, C in which any H can be replaced by F) 1-4 alkanes, etc.), or a combination thereof.
[0099] The typical procedure for preparing block copolymers is as follows. A monomer mixture is typically prepared in a solvent and combined with an initiator. The solution can be degassed with nitrogen and introduced into a syringe as a feed mixture. Then part of the feed mixture can be added to a heated reaction vessel containing a chain transfer agent, and polymerization can be allowed to proceed for a period of time to form the first block of the block copolymer. Subsequently, the second part of the feed mixture can be added to the heated reaction vessel, and polymerization can be allowed to proceed for a period of time to form the second block of the block copolymer. The additional blocks of the copolymer can be formed using a similar sequence of steps. Although the above examples provide a single feed mixture, wherein the ratio of monomers remains constant for each subsequently formed block of the block copolymer, in other embodiments, different feed mixtures can be added in each step to change the ratio of monomers for each block of the block copolymer. For block copolymers comprising additional blocks other than the first block and the second block as described herein, different feed mixtures can be used to form the third block and subsequent blocks so that each block can have the same or different monomer composition and / or ratio.
[0100] After the polymerization is complete, the formed block copolymer is separated. The separation step can be performed by known procedures and can include evaporating any residual monomer and / or solvent, precipitating in a suitable solvent, filtering or centrifuging the precipitated block copolymer, washing the block copolymer, and drying the washed block copolymer. The transition metal compound can be removed by passing through a column or pad of aluminum oxide, silicon dioxide and / or clay. Alternatively, the transition metal compound can be oxidized (if necessary) and retained in the block copolymer as a stabilizer. The chain termination group (when present) can be cleaved from the block copolymer using any suitable method known in the art.
[0101] Precipitation can typically be performed using a suitable C 5-8 Alkanes or C 5-8 Cycloalkane solvents such as pentane, hexane, heptane, cyclohexane, or mineral spirits, or C 1-6 The reaction can be carried out using an alcohol such as methanol, ethanol, or isopropanol, or a combination of suitable solvents.
[0102] A photoresist composition is also provided, comprising a block copolymer as described herein and a solvent. In certain embodiments, the photoresist composition may comprise a block copolymer as described herein, a photoacid generator, and a solvent. In still other embodiments, the photoresist composition may comprise a first polymer, a photoacid generator, and a solvent that are block copolymers as described herein, and may further comprise a second (different) polymer that is structurally different from the first polymer (block copolymer).
[0103] The second polymer may include one or more polymerization (e.g., repeating) units, such as those described herein. Exemplary second polymers may be polyacrylates, polyvinyl ethers, polyesters, polynorbornenes, polyacetals, polyethylene glycols, polyamides, polyacrylamides, polyphenols, novolacs, styrene polymers, polyvinyl alcohol, or combinations thereof. For example, the second polymer may include repeating units containing acid-labile groups, hydroxyaryl groups, fluoroalcohol groups, sulfonamide groups, lactone groups, or combinations thereof.
[0104] M of the second polymer w Typically, it is 1,000 to 50,000 g / mol, particularly 2,000 to 30,000 g / mol, more particularly 3,000 to 20,000 g / mol, still more particularly 3,000 to 10,000 g / mol. The PDI of the polymer (which is M w With M n The ratio of ) is typically 1.1 to 3, and in particular 1.1 to 2. The molecular weight is determined by GPC using polystyrene standards.
[0105] The second polymer can be prepared using any suitable method in the art. For example, one or more monomers corresponding to the polymerized units described herein can be combined or fed separately using one or more suitable solvents and initiators and polymerized in a reactor. For example, the second polymer can be obtained by polymerization of the corresponding monomers under any suitable conditions, such as by heating at an effective temperature, irradiating with actinic radiation at an effective wavelength, or a combination thereof.
[0106] The photoresist composition comprises a solvent for dissolving the components of the composition and facilitating its coating on the substrate. Preferably, the solvent is an organic solvent conventionally used in the manufacture of electronic devices. Suitable solvents include, for example: aliphatic hydrocarbons such as hexane and heptane; aromatic hydrocarbons such as toluene and xylene; halogenated hydrocarbons such as dichloromethane, 1,2-dichloroethane and 1-chlorohexane; alcohols such as methanol, ethanol, 1-propanol, isopropanol, tert-butanol, 2-methyl-2-butanol and 4-methyl-2-pentanol; propylene glycol monomethyl ether (PGME), ethers such as diethyl ether, tetrahydrofuran, 1,4-dioxane and anisole; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, 2-heptanone and cyclohexanone (CHO); esters such as acetic acid Ethyl acetate, n-butyl acetate, propylene glycol monomethyl ether acetate (PGMEA), ethyl lactate (EL), methyl hydroxyisobutyrate (HBM) and ethyl acetoacetate; lactones such as γ-butyrolactone (GBL) and ε-caprolactone; lactams such as N-methylpyrrolidone; nitriles such as acetonitrile and propionitrile; cyclic or non-cyclic carbonates such as propylene carbonate, dimethyl carbonate, ethylene carbonate, propylene carbonate, diphenyl carbonate, and propylene carbonate; polar aprotic solvents such as dimethyl sulfoxide and dimethylformamide; water; and combinations thereof. Among these, preferred solvents are PGME, PGMEA, EL, GBL, HBM, CHO, and combinations thereof. The total solvent content (i.e., the cumulative solvent content of all solvents) in the photoresist composition is typically 40 weight percent (wt%) to 99 wt%, more typically 70 wt% to 99 wt%, and still more typically 85 wt% to 99 wt%, based on the total weight of the photoresist composition. The desired solvent content will depend on, for example, the desired thickness of the applied photoresist layer and the coating conditions.
[0107] In the photoresist composition, the block copolymer can be present in the photoresist composition in an amount of 10 wt % to 99.9 wt %, typically 25 wt % to 99 wt %, and more typically 50 wt % to 95 wt % based on the total solids of the photoresist composition. It will be understood that the total solids include the block copolymer, one or more PAGs, and other non-solvent components.
[0108] The photoresist composition may further include a photoacid generator (PAG). The PAG may be in an ionic or nonionic form. The PAG may be in a polymeric or non-polymeric form. When in a polymeric form, the PAG may exist as part of a repeating unit of a polymer derived from a polymerizable PAG monomer. In some embodiments, the block copolymer may further include a repeating unit that includes a PAG functional group (e.g., a salt group as a repeating unit).
[0109] Suitable PAG compounds may have the formula G + A -, where G + is a photoactive cation and A - The PAG anion is an anion that can generate a photoacid. The PAG cation is preferably selected from an onium cation, preferably an iodonium or sulfonium cation. Particularly suitable anions include those having a conjugate acid pKa of -15 to 10. The PAG anion is typically an organic anion having a sulfonate group or a non-sulfonate group such as a sulfonamidate, a sulfonimidate, a methide, or a borate.
[0110] In some embodiments, the PAG cation can be a sulfonium cation or an iodonium cation. For example, the PAG cation can be a sulfonium cation having formula (10) or an iodonium cation having formula (11):
[0111] In equations (10) and (11), R 17 To R 21 may be independently substituted or unsubstituted C 1-20 Alkyl, substituted or unsubstituted C 3-20 Cycloalkyl, substituted or unsubstituted C 2-20 Alkenyl, substituted or unsubstituted C 6-30 Aryl, substituted or unsubstituted C 6-30 Iodoaryl, substituted or unsubstituted C 3-30 Heteroaryl, substituted or unsubstituted C 7-20 Arylalkyl, or substituted or unsubstituted C 4-20 Heteroarylalkyl, or a combination thereof. 17 To R 19 Each of the may be alone or connected to R via a single bond or a divalent linking group 17 To R 19 Another group in to form a ring. 20 and R 21 R may be alone or connected to each other via a single bond or a divalent linking group to form a ring. 17 To R 21 Each of may optionally include a divalent linking group as part of its structure. 17 To R 21 Each of which independently may optionally include an acid-labile group selected from, for example, a tertiary alkyl ester group, a secondary or tertiary aryl ester group, a secondary or tertiary ester group having a combination of an alkyl group and an aryl group, a tertiary alkoxy group, an acetal group, or a ketal group.
[0112] Exemplary sulfonium cations having formula (10) may include one or more of the following:
[0113] Exemplary iodonium cations having formula (11) may include one or more of the following:
[0114] Exemplary organic anions having a sulfonate group may include one or more of the following:
[0115] Exemplary non-sulfonated anions may include one or more of the following:
[0116] Commonly used onium salts may include, for example, triphenylsulfonium trifluoromethanesulfonate, (p-tert-butoxyphenyl)diphenylsulfonium trifluoromethanesulfonate, tri(p-tert-butoxyphenyl)sulfonium trifluoromethanesulfonate, triphenylsulfonium p-toluenesulfonate; di-tert-butylphenyliodonium perfluorobutanesulfonate, and di-tert-butylphenyliodonium camphorsulfonate. Other useful PAG compounds are known in the art of chemically amplified photoresists and include, for example: nonionic sulfonyl compounds, such as 2-nitrobenzyl p-toluenesulfonate, 2,6-dinitrobenzyl p-toluenesulfonate, and 2,4-dinitrobenzyl p-toluenesulfonate; sulfonate esters, such as 1,2,3-tris(methylsulfonyloxy)benzene, 1,2,3-tris(trifluoromethanesulfonyloxy)benzene, and 1,2,3-tris(p-toluenesulfonyloxy)benzene; diazomethane derivatives, such as bis(phenylsulfonyl)diazomethane, bis(p-toluenesulfonyl)diazomethane, and bis(p-toluenesulfonyl)diazomethane. Methane; glyoxime derivatives, such as bis-O-(p-toluenesulfonyl)-α-dimethylglyoxime, and bis-O-(n-butanesulfonyl)-α-dimethylglyoxime; sulfonate derivatives of N-hydroxyimide compounds, such as N-hydroxysuccinimide methanesulfonate, N-hydroxysuccinimide trifluoromethanesulfonate; and halogen-containing triazine compounds, such as 2-(4-methoxyphenyl)-4,6-bis(trichloromethyl)-1,3,5-triazine, and 2-(4-methoxynaphthyl)-4,6-bis(trichloromethyl)-1,3,5-triazine. Suitable photoacid generators are further described in U.S. Pat. Nos. 8,431,325 and 4,189,323.
[0117] Typically, when the photoresist composition contains a non-polymeric PAG, the PAG is present in the photoresist composition in an amount of 0.1 wt% to 55 wt%, more typically 1 wt% to 25 wt%, based on the total solids of the photoresist composition. When present in polymeric form, the PAG is typically contained in the polymer in an amount of 1 mol% to 25 mol%, more typically 1 mol% to 20 mol%, or 2 mol% to 10 mol%, based on the total polymerized units in the polymer.
[0118] In some respects, the negatively charged ion and / or cation of PAG do not include and do not contain-F,-CF3 or-CF2-group.It should be understood that "does not contain-F,-CF3 or-CF2-group" means that the negatively charged ion and / or cation of PAG do not include groups such as-CH2CF3 and-CH2CF2CH3.In other respects, the negatively charged ion and / or cation of PAG do not contain fluorine (that is, do not contain fluorine atoms and are not replaced by fluorine-containing groups).In some respects, the photoacid generator does not contain fluorine (that is, both photoactive cations and negatively charged ions do not contain fluorine).
[0119] In some aspects, the photoresist composition may further include a surfactant. Preferably, the surfactant is hydrophobic, and is substantially not miscible with the block copolymer and other solid components of the photoresist composition and has a surface energy lower than them. When applied on a substrate, the surfactant can be separated from the other solid components of the photoresist composition to reach the top surface of the photoresist layer formed. When applied on a substrate, the surfactant can provide a useful surface property for the photoresist composition. For example, in an immersion exposure process, the surfactant can be used as a barrier layer between an immersion fluid (typically water, between the lenses of an intercalated exposure tool) and a photoresist layer. This can minimize or prevent the components of the lower part of the photoresist from leaching into the immersion fluid, otherwise it may cause the pollution of the lens and change the effective refractive index and transmission characteristics of the immersion fluid. Due to its hydrophobic nature, the surfactant can allow a high receding contact angle relative to the immersion fluid, which can allow a faster scanning speed and increased process throughput. In both immersion and non-immersion exposure processes, surface active materials can also have a beneficial effect on reducing defect rates, such as patterning defects, such as closed contacts and bridging defects in line-space patterns.
[0120] The surface active material is preferably soluble in the developer, or becomes soluble in the developer during patterning, such as by interacting with the photoacid produced or with the developer. In some aspects, the surface active material can be a polymer material. The surface active material can be a homopolymer or a copolymer comprising two, three or more different types of repeating units. In some aspects, the surface active material can be non-polymeric, in the form of a single molecule. Suitable for the surface active material is to include, for example, one or more groups selected from the following: acid groups such as carboxylic acid groups or sulfonic acid groups, acid unstable groups, base unstable groups, base soluble groups such as fluoroalcohols or phenol groups, alkyl groups, fluoroalkyl groups, ester groups, and combinations thereof. In the case of aqueous alkaline developers such as 0.26 equivalent (N) tetramethylammonium hydroxide (TMAH) aqueous solutions, the surface active polymer preferably includes one or more base unstable or base soluble groups to improve solubility in the developer solution after exposure to activating radiation and post-exposure baking.
[0121] When present, the surface active material is typically present in the photoresist composition in an amount of 0.01 wt % to 10 wt %, typically 1 wt % to 5 wt %, based on the total solids of the photoresist composition.
[0122] The photoresist composition may further comprise one or more additional optional additives. For example, optional additives may include actinic dyes and contrast dyes, anti-striation agents, plasticizers, speed increasers, sensitizers, photodecomposable quenchers (PDQ) (also referred to as photodecomposable bases), alkaline quenchers, thermal acid generators, surfactants, etc., or combinations thereof. If present, optional additives are typically present in the photoresist composition in an amount of 0.01 wt % to 10 wt % based on the total solids of the photoresist composition.
[0123] PDQ generates a weak acid upon irradiation. The acid generated by the photodegradable quencher is not strong enough to react rapidly with the acid-labile groups present in the resist matrix. Exemplary photodegradable quenchers include, for example, anions of weak acids (pKa>1) such as C 1-20 Carboxylic acid or C 1-20 The photodecomposable quencher is a photodecomposable organic zwitterionic compound such as diphenyliodonium-2-carboxylate.
[0124] PDQ may be in non-polymeric or polymer-bound form.The polymeric unit containing the photodecomposable quencher is typically present in an amount of 0.1 mol% to 30 mol%, preferably 1 mol% to 10 mol% and more preferably 1 mol% to 2 mol% based on the total repeating units of the polymer.
[0125] Exemplary basic quenchers include, for example, linear aliphatic amines such as tributylamine, trioctylamine, triisopropanolamine, tetrakis(2-hydroxypropyl)ethylenediamine, n-tert-butyldiethanolamine, tris(2-acetoxy-ethyl)amine, 2,2',2",2"'-(ethane-1,2-diylbis(azanetriyl))tetraethanol, 2-(dibutylamino)ethanol, and 2,2',2"-nitrilotriethanol; cyclic aliphatic amines such as 1- (tert-Butyloxycarbonyl)-4-hydroxypiperidine, tert-butyl 1-pyrrolidinecarboxylate, tert-butyl 2-ethyl-1H-imidazole-1-carboxylate, di-tert-butyl piperazine-1,4-dicarboxylate, and N-(2-acetoxy-ethyl)morpholine; aromatic amines such as pyridine, di-tert-butylpyridine, and pyridinium; linear and cyclic amides and their derivatives such as N,N-bis(2-hydroxyethyl)palmitamide, N,N-diethylacetamide, N 1 ,N 1 ,N 3 ,N 3 -tetrabutylmalonamide, 1-methylazacycloheptan-2-one, 1-allylazacycloheptan-2-one, and tert-butyl 1,3-dihydroxy-2-(hydroxymethyl)propan-2-ylcarbamate; ammonium salts such as quaternary ammonium salts of sulfonates, sulfamates, carboxylates, and phosphonates; imines such as primary and secondary aldimines and ketimines; diazines such as optionally substituted pyrazines, piperazines, and phenazines; diazoles such as optionally substituted pyrazoles, thiadiazoles, and imidazoles; and optionally substituted pyrrolidones such as 2-pyrrolidone and cyclohexylpyrrolidine.
[0126] The basic quencher may be in a non-polymeric or polymer-bound form. When in a polymeric form, the quencher may be present in the repeating unit of the polymer. The repeating unit containing the quencher is typically present in an amount of 0.1 mol% to 30 mol%, preferably 1 mol% to 10 mol% and more preferably 1 mol% to 2 mol% based on the total repeating units of the polymer.
[0127] Exemplary surfactants include fluorinated and non-fluorinated surfactants and can be ionic or non-ionic, with non-ionic surfactants being preferred. Exemplary fluorinated non-ionic surfactants include perfluorinated C4 surfactants, such as FC-4430 and FC-4432 surfactants (3M Corporation); and fluorinated glycols, such as POLYFOX TMPF-636, PF-6320, PF-656 and PF-6520 fluorosurfactants (Omnova). In one aspect, the photoresist composition further comprises a surfactant polymer comprising a fluorine-containing repeating unit.
[0128] Methods of forming a pattern are also provided. According to one aspect, the method of forming a pattern comprises applying a layer of a photoresist composition on a substrate to form a photoresist composition layer; exposing the photoresist composition layer to activating radiation in a patternwise manner to form an exposed photoresist composition layer; and developing the exposed photoresist composition layer to provide a resist relief image. The photoresist composition comprises a block copolymer as described herein and a solvent.
[0129] Patterning methods using the photoresist compositions of the present invention will now be described. Suitable substrates on which the photoresist compositions may be applied include electronic device substrates. A wide variety of electronic device substrates may be used in the present invention, such as semiconductor wafers; polycrystalline silicon substrates; packaging substrates, such as multi-chip modules; flat panel display substrates; substrates for light emitting diodes (LEDs) including organic light emitting diodes (OLEDs); etc., wherein semiconductor wafers are typical. Such substrates are typically made of one or more of silicon, polycrystalline silicon, silicon oxide, silicon nitride, silicon oxynitride, silicon germanium, gallium arsenide, aluminum, sapphire, tungsten, titanium, titanium-tungsten, nickel, copper, and gold. Suitable substrates may be in the form of wafers, such as those used to manufacture integrated circuits, optical sensors, flat panel displays, integrated optical circuits, and LEDs. Such substrates may have any suitable size. Typical wafer substrate diameters are 200 to 300 millimeters (mm), although wafers with smaller and larger diameters may be appropriately used according to the present invention. The substrate may include one or more layers or structures, which may optionally include an active or operable portion of a formed device.
[0130] Typically, one or more photolithographic layers, such as a hard mask layer (e.g., spin-on carbon (SOC), amorphous carbon, or a metal hard mask layer), a CVD layer (e.g., a silicon nitride (SiN), silicon oxide (SiO), or silicon oxynitride (SiON) layer), an organic or inorganic underlayer, or a combination thereof, are provided on the upper surface of the substrate prior to coating the photoresist composition of the present invention. Such layers together with the overcoated photoresist layer form a photolithographic material stack.
[0131] Alternatively, an adhesion promoter layer may be applied to the substrate surface prior to coating the photoresist composition. If an adhesion promoter is desired, any suitable adhesion promoter for polymer films may be used, such as a silane, typically an organosilane such as trimethoxyvinylsilane, triethoxyvinylsilane, hexamethyldisilazane, or an aminosilane coupling agent such as γ-aminopropyltriethoxysilane. Particularly suitable adhesion promoters include those available from DuPont Electronics & Industrial (Marlborough, Massachusetts) as AP TM 3000, AP TM 8000 and AP TM Those sold under the 9000S name.
[0132] Photoresist composition can be coated on substrate by any suitable method, including spin coating, spray coating, dip coating, scraper etc. For example, applying photoresist layer can be completed by using coating track to spin-coat photoresist in solvent, wherein photoresist is distributed on rotating wafer. During distribution, wafer is typically rotated for 15 to 120 seconds at a speed of up to 4,000 rpm (rpm), such as 200 to 3,000 rpm, such as 1,000 to 2,500 rpm to obtain photoresist composition layer on substrate. It will be appreciated by those skilled in the art that the thickness of the layer applied can be adjusted by changing the total solids of rotation speed and / or composition. The photoresist composition layer formed by the composition of the present invention typically has a dry layer thickness of 3 to 30 microns (μm), preferably greater than 5 to 30 μm and more preferably 6 to 25 μm.
[0133] Next, the photoresist composition is typically soft-baked to minimize the solvent content in the layer, thereby forming a non-sticky coating and improving the adhesion of the layer to the substrate. Soft baking is carried out, for example, on a hot plate or in an oven, wherein the hot plate is typical. The soft baking temperature and time will depend on, for example, the photoresist composition and thickness. The soft baking temperature is typically 80°C to 170°C and more typically 90°C to 150°C. The soft baking time is typically 10 seconds to 20 minutes (min), more typically 1 minute to 10 minutes, and also more typically 1 minute to 2 minutes. Those of ordinary skill in the art can easily determine the heating time based on the components of the composition.
[0134] Next, the photoresist layer is exposed to activating radiation in a patterned manner to produce a solubility difference between the exposed area and the unexposed area. The exposure of the photoresist composition to the radiation having an activating effect on the composition mentioned herein shows that radiation can form a latent image in the photoresist composition. Exposure is typically carried out by a patterned photomask, and the photomask has optically transparent areas and optically opaque areas corresponding to the resist layer area to be exposed and the unexposed resist layer area, respectively. Alternatively, this exposure can be carried out in the absence of a photomask with a direct writing method, which is typically used for electron beam lithography. Activating radiation typically has a wavelength less than 400 nanometers (nm), less than 300nm or less than 200nm, wherein the wavelength of 248nm (KrF), 193nm (ArF), 13.5nm (EUV) or electron beam lithography is preferred. Preferably, activating radiation is 193nm radiation or EUV wavelength. These methods can be used in immersion or dry (non-immersion) lithography. The exposure energy is typically 1 to 200 mJ / cm2. 2 ), preferably 10 to 100 mJ / cm 2 and more preferably 20 to 50 mJ / cm 2 , which depends on the exposure tool and the components of the photoresist composition.
[0135] After exposing the photoresist layer, a post-exposure bake (PEB) of the exposed photoresist layer is performed. PEB can be performed, for example, on a hot plate or in an oven, where a hot plate is typical. The conditions of PEB will depend, for example, on the photoresist composition and the layer thickness. PEB is typically performed at a temperature of 70°C to 150°C, preferably 75°C to 120°C, and a time of 30 to 120 seconds. A latent image defined by polarity switching regions (exposed regions) and polarity unswitched regions (unexposed regions) is formed in the photoresist.
[0136] Then, the exposed photoresist layer is developed with a suitable developer to selectively remove those regions of the layer that are soluble in the developer, while the remaining insoluble regions form the resulting photoresist pattern relief image. In the case of a positive development (PTD) process, the exposed regions of the photoresist layer are removed during development and unexposed regions are retained. On the contrary, in a negative development (NTD) process, the exposed regions of the photoresist layer are retained during development and unexposed regions are removed. The application of the developer can be completed by any suitable method, as described above for the application of photoresist compositions, wherein spin coating is typical. The development time is the time period for effectively removing the soluble regions of the photoresist, wherein 5 seconds to 60 seconds is typical. Development is typically carried out at room temperature.
[0137] Suitable developers for PTD processes include aqueous alkaline developers, such as quaternary ammonium hydroxide solutions, such as TMAH (preferably 0.26N TMAH), tetraethylammonium hydroxide, tetrabutylammonium hydroxide, sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, etc. Suitable developers for NTD processes are based on organic solvents, meaning that the cumulative content of organic solvents in the developer is 50 wt% or more, typically 95 wt% or more, 98 wt% or more, or 100 wt% based on the total weight of the developer. Suitable organic solvents for NTD developers include, for example, those selected from ketones, esters, ethers, hydrocarbons, and mixtures thereof. The developer is typically 2-heptanone or n-butyl acetate.
[0138] A coated substrate can be formed from the photoresist composition of the present invention. Such a coated substrate comprises: (a) a substrate having one or more layers to be patterned on its surface; and (b) a photoresist composition layer on the one or more layers to be patterned.
[0139] The photoresist pattern can be used as, for example, an etching mask, whereby the pattern is transferred to one or more sequentially arranged lower layers by known etching techniques, typically by dry etching (such as reactive ion etching). The photoresist pattern can be used, for example, to transfer the pattern to the following hard mask layer, which in turn is used as an etching mask for transferring the pattern to one or more layers below the hard mask layer. If during the pattern transfer, the photoresist pattern is not lost, it can be removed from the substrate by known techniques (such as oxygen plasma ashing). When used for one or more such patterning processes, the photoresist composition can be used to manufacture semiconductor devices, such as storage devices, processor chips (CPUs), graphics chips, optoelectronic chips, LEDs, OLEDs, and other electronic devices.
[0140] The present invention is further illustrated by the following non-limiting examples. Examples Synthesis Example
[0141] The synthesis reaction was carried out under nitrogen atmosphere. 2,2'-azobis(methyl 2-methylpropionate) (V601) and 1,1'-azobis(cyclohexane-1-carbonitrile) (V40) initiators were purchased from Wako Specialty Chemicals. Diphenyliodonium-2-carboxylate monohydrate (DPIC), diphenyl(p-phenyl)sulfonium 2-(((3r,5r,7r)-adamantane-1-carbonyl)oxy)-1,1-difluoroethane-1-sulfonate (TDPS IAD), 4-(4-(tert-butyl)phenyl)-1,4-oxathian-4-ium tris((trifluoromethyl)sulfonyl)methanide (TBPTO C1), ethyl cyclopentyl methacrylate (ECPMA), γ-butyrolactone-2-yl methacrylate (α-GBLMA), 2-oxohexahydro-2H-3,5-methylenecyclopenta[b]furan-6-yl methacrylate (NLMA), propylene glycol monomethyl ether acetate (PGMEA), anisole, ethoxymethyl methacrylate (EOMMA), 5-methyl-3-methylenedihydrofuran-2(3H)-one (aMMBL), 2-(adamantan-1-yl)propan-2-yl methacrylate (IAM), 3-hydroxyadamantan-1-yl methacrylate (HAMA), (cyclohexyloxy)methyl methacrylate (CHOMMA), and 2-cyano-2-propyldodecyl trithiocarbonate were purchased from commercial sources and used without further purification. Synthesis of ECPMA / α-GBLMA / NLMA Copolymer Synthesis of triblock copolymer (ECPMA / α-GBLMA / NLMA)
[0142] Prepare triblock copolymers 1 to 4 as follows. A mixture of 26.1 grams (g) of ECPMA, 23.0g of α-GBLMA and 15.3g of NLMA was mixed with 40.0g of anisole to provide a monomer solution having a solid content of 62wt%. In a separate vial, 92 milligrams (mg) of V40 initiator were loaded into 22.3g of the original monomer solution. The solution was degassed with nitrogen and introduced into a syringe as a feed mixture. In a reactor, 318mg of trithiocarbonic acid 2-cyano-2-propyl dodecyl ester was used as a chain transfer agent (CTA) and protected at 110°C under N2. One third of the feed mixture was added to the reactor, and the resulting reaction mixture was heated for 120 minutes. Then, another one third of the feed mixture was added to the reactor, and the reaction mixture was heated for another 120 minutes. Then, the last one third of the feed mixture was added to the reactor, and the reaction mixture was heated for 120 minutes. When analysis was required, aliquots were taken from the reaction mixture under a gentle stream of N2. The triblock copolymers were isolated by precipitation into isopropanol. Conversions of >90% were achieved at the end of each block polymerization. Synthesis of multi-block copolymers. (ECPMA / α-GBLMA / NLMA)
[0143] Multi-block copolymer 5 was prepared as follows. A mixture of 8.83 g ECPMA, 7.51 g α-GBLMA and 5.01 g NLMA was mixed with 14.21 g anisole to provide a monomer solution having a solid content of 60 wt%. In a separate vial, 162 mg V40 initiator was loaded into 12.99 g of the original monomer solution. The solution was degassed with nitrogen and introduced into a syringe as a feed mixture. In the reactor, 225 mg trithiocarbonic acid 2-cyano-2-propyl dodecyl ester was used as CTA and protected at 110 ° C under N2. One seventh of the feed mixture was added to the reactor per hour, and an aliquot was taken out from the reaction mixture under a gentle N2 flow when needed. The polymer was separated by precipitation into isopropanol. The conversion rate reached>90% at the end of each block polymerization. End group removal
[0144] The end groups were removed from copolymers 2, 4 and 5 by using the following procedure. The corresponding block copolymers were dissolved in PGMEA (to provide a solid content of 15 wt %) under mild heating. After cooling to less than 40° C., 20 equivalents of V601 initiator (relative to the trithiocarbonate groups of the block copolymer) were added to the solution. The solution was heated to 80° C. for 3 hours and precipitated into isopropanol to obtain a block copolymer without trithiocarbonate end groups. Comparison of copolymers. (ECPMA / α-GBLMA / NLMA)
[0145] Random copolymer 6 (comparison) was prepared as follows. A degassed mixture of 112 g of ethyl lactate (70 wt%) and 1,4-lactone (30 wt%) was charged into the reactor and heated to 80 ° C. A degassed monomer feed solution was prepared by a combination of 318.3 g of solvent (ethyl lactate / 1,4-lactone, 7:3 w / w), 95.9 g of ECPMA, 88.9 g of α-GBLMA, and 58 g of NLMA. Separately, a degassed initiator feed solution was prepared using 12.4 g of V601 initiator and 125.2 g of solvent (ethyl lactate / 1,4-lactone, 7:3 w / w). Then, the monomer feed solution and the initiator feed solution were added to the reactor simultaneously and continuously, wherein the monomer feed solution was added over a course of 240 minutes, and the initiator feed solution was added over a course of 210 minutes. The reactor was then cooled to ambient temperature at a rate of 1 ° C / min. The copolymer was isolated by precipitation into methanol and the product was dried before use.
[0146] Prepare random copolymer 7 (comparison) as follows. 11.2g of degassed PGMEA is loaded into the reactor and heated to 80°C. Degassed monomer feed solution is prepared by the combination of 10.245g ECPMA, 9.556g α-GBLMA and 6.244g NLMA. Separately, 1.541g V601 initiator and 13.902g PGMEA are used to prepare degassed initiator feed solution. Then, monomer feed solution and initiator feed solution are added to the reactor simultaneously and continuously, wherein monomer feed solution is added over a course of 240 minutes, and initiator feed solution is added over a course of 210 minutes. Five hours after the feed solution starts, the reactor is then cooled to ambient temperature at a rate of 1°C / min. Copolymer is separated by being precipitated into methanol, and the product is dried before use.
[0147] Block copolymers derived from the monomer combination ECPMA / α-GBLMA / NLMA (40 / 40 / 20 molar ratio) and comparative copolymers are summarized in Table 1. Table 1 M w 、M n , and dispersion index Determined by GPC using polystyrene standards. Synthesis of Additive E1
[0148] A monomer solution was prepared by combining 192.00 g GMEA, 133.2 g (methacryloyloxy) methylene bis (2,2-difluoro-3,3-dimethylbutyrate) and 8.51 g ethyl cyclopentyl methacrylate in a flask and stirring the resulting mixture to dissolve the components. Separately, an initiator solution was prepared by combining 10.72 g PGMEA and 6.2 g V601 initiator in a flask. 20.05 g PGMEA was introduced into a separate reaction vessel and the vessel was purged with nitrogen for 30 minutes. Next, the reaction vessel was heated to 95 ° C under stirring. Then, the monomer solution and the initiator solution were introduced into the reaction vessel as separate feeds over a period of 2.5 hours. After 2.5 hours were completed, the reaction vessel was maintained at 95 ° C for an additional 3 hours under stirring, and then allowed to cool to room temperature. M was obtained. w / M n (kg / mol) of Additive El 9.658 / 6.192 as determined by GPC using polystyrene standards. Photoresist preparation.
[0149] Positive photoresist compositions PR1 to PR11 were prepared by dissolving the solid components (copolymer, PAG, quencher and additive) in a solvent using the materials and amounts indicated in Table 2, wherein the amounts are expressed in wt% based on 100wt% of the total weight of solids. The total solids content of the photoresist composition was 3.1%. The solvent system contained PGMEA (S1) and methyl 2-hydroxyisobutyrate (S2). Each mixture was shaken on a mechanical shaker in a 100 mL glass container and filtered through a PTFE disc filter having a pore size of 0.20 microns. Table 2 Lithography Tests - Examples 1 to 14 E 尺寸 , EL% and LWR evaluation
[0150] Use 205℃ curing temperature with AR TM 40A antireflective agent (DuPont Electronics & Industries) was spin-coated on a 300 mm silicon wafer for 60 seconds to form a first BARC layer with a thickness of 80 nm. The AR TMThe wafer was spin coated with 104 antireflective agent (DuPont Electronics & Industries) for 60 seconds to form a second BARC layer with a thickness of 40 nm. The wafer was then spin coated with the corresponding photoresist composition from Table 2 and soft baked at 90° C. for 60 seconds to provide a photoresist layer with a thickness of 90 nm. The wafer was then spin coated with 104 antireflective agent (DuPont Electronics & Industries) for 60 seconds to form a second BARC layer with a thickness of 40 nm. The wafer was then spin coated with the corresponding photoresist composition from Table 2 and soft baked at 90° C. for 60 seconds to provide a photoresist layer with a thickness of 90 nm. TM LITHIUS TM The coating tool coated the BARC and photoresist layers. Using a Nikon S610C immersion scanner (1.30NA, 0.98 / 0.79 inner / outer σ, dipole illumination with 35Y polarization), the wafer was exposed to various doses of 193nm activating radiation using a mask with a line-space pattern (38nm line width / 80nm spacing or 38nm line width / 86nm spacing). The exposed wafer was post-exposure baked at 95°C for 60 seconds and washed with 0.26N tetramethylammonium hydroxide (TMAH) aqueous solution (MF TM -CD26, DuPont Electronics & Industrial Company) for 12 seconds. The wafer was then rinsed with DI water and spin dried to form a photoresist pattern. CD line width measurements of the formed patterns were performed using a Hitachi High Technologies Co. CG4000 CD-SEM.
[0151] The critical dimension (CD) of the line-space pattern in nanometers (nm) is analyzed, where the patterning energy “E 尺寸 ” is the irradiation energy when the CD of the formed line-space pattern is equal to the CD of the mask pattern. E 尺寸 mJ / cm 2 ). Exposure latitude (EL%) is the difference in exposure energy required to print a line-space pattern at plus or minus 10% of the target diameter, normalized by the set energy. Line width roughness (LWR) is expressed in nanometers (nm) and is determined as a 3-σ value from the distribution of a total of 100 arbitrary points of line width measurement, followed by removal of metrology noise. E 尺寸 , EL% and LWR data are shown in Table 3a and Table 3b. E0 Evaluation
[0152] Use 205℃ curing temperature with AR TM A 200 mm silicon wafer was spin coated with 40A antireflective agent (DuPont Electronics & Industries) for 60 seconds to form a BARC layer with a thickness of 80 nm. The wafer was then spin coated with the corresponding photoresist composition from Table 2 and soft baked at 90°C for 60 seconds to provide a photoresist layer with a thickness of 90 nm. The TEL CLEAN TRACK TM ACT TMBARC and photoresist layers were coated using an ASML 1100 scanner (0.75NA, 0.89 / 0.64 inner / outer σ, with quadrupole-30) to expose the wafers to various doses of 193nm activating radiation. The exposed wafers were post-exposure baked at 95°C for 60 seconds and treated with 0.26N TMAH aqueous solution (MF TM -CD26, DuPont Electronics & Industries) for 60 seconds. The wafer was then rinsed with DI water and spun dry. Film thickness was measured at each exposure area using a KLA Therma-Wave Opti-Probe 7341 and plotted against dose. E0 values (mJ / cm 2 ) was determined as the first dose value at which the remaining film thickness was less than 7% of the original coating thickness. The E0 data are shown in Table 3a and Table 3b. Table 3a Table 3b Lithography Tests - Examples 15 to 30 E 尺寸 , EL%, LWR and PCM evaluation
[0153] Use 205℃ curing temperature with AR TM 40A antireflective agent (DuPont Electronics & Industries) was spin-coated on a 300 mm silicon wafer for 60 seconds to form a first BARC layer with a thickness of 80 nm. The AR TM The wafer was spin coated with 104 antireflective agent (DuPont Electronics & Industries) for 60 seconds to form a second BARC layer with a thickness of 40 nm. The wafer was then spin coated with the corresponding photoresist composition from Table 2 and soft baked at 90° C. for 60 seconds to provide a photoresist layer with a thickness of 90 nm. The wafer was then spin coated with 104 antireflective agent (DuPont Electronics & Industries) for 60 seconds to form a second BARC layer with a thickness of 40 nm. The wafer was then spin coated with the corresponding photoresist composition from Table 2 and soft baked at 90° C. for 60 seconds to provide a photoresist layer with a thickness of 90 nm. TM LITHIUS TM The coating tool coated the BARC and photoresist layers. Using an ASML 1900i immersion scanner (1.35NA, 0.988 / 0.90 inner / outer σ, dipole illumination with 35Y polarization), the wafer was exposed to various doses of 193nm activating radiation using a mask with a 1:1 line-space pattern (38nm line width / 76nm spacing or 37nm line width / 74nm spacing). The exposed wafer was post-exposure baked at 95°C for 60 seconds and washed with 0.26N tetramethylammonium hydroxide (TMAH) aqueous solution (MF TM-CD26, DuPont Electronics & Industries) for 12 seconds. The wafer was then rinsed with DI water and spin dried to form a photoresist pattern. CD line width measurements of the formed pattern were performed using a Hitachi High-Tech CG4000 CD-SEM.
[0154] The critical dimension (CD) of the line-space pattern in nanometers (nm) is analyzed, where the patterning energy “E 尺寸 ” is the irradiation energy when the CD of the formed line-space pattern is equal to the CD of the mask pattern. E 尺寸 mJ / cm 2 ). Exposure latitude (EL%) is the difference in exposure energy required to print a line-space pattern at plus or minus 10% of the target diameter, normalized by the set energy. Line width roughness (LWR) is expressed in nanometers (nm) and is determined as a 3-σ value from the distribution of a total of 100 arbitrary points of line width measurement, followed by removal of metrology noise. PCM is pattern collapse margin, which is expressed in nanometers. E 尺寸 , EL%, LWR and PCM data are shown in Table 4a and Table 4b. E0 Evaluation
[0155] Use 205℃ curing temperature with AR TM A 200 mm silicon wafer was spin coated with 40A antireflective agent (DuPont Electronics & Industries) for 60 seconds to form a BARC layer with a thickness of 80 nm. The wafer was then spin coated with the corresponding photoresist composition from Table 2 and soft baked at 90°C for 60 seconds to provide a photoresist layer with a thickness of 90 nm. The TEL CLEAN TRACK TM ACT TM BARC and photoresist layers were coated using an ASML 1100 scanner (0.75NA, 0.89 / 0.64 inner / outer σ, with quadrupole-30) to expose the wafers to various doses of 193nm activating radiation. The exposed wafers were post-exposure baked at 95°C for 60 seconds and treated with 0.26N TMAH aqueous solution (MF TM -CD26, DuPont Electronics & Industries) for 60 seconds. The wafer was then rinsed with DI water and spun dry. Film thickness was measured at each exposure area using a KLA Therma-Wave Opti-Probe 7341 and plotted against dose. E0 values (mJ / cm 2 ) was determined as the first dose value at which the remaining film thickness was less than 7% of the original coating thickness. The E0 data are shown in Table 4a and Table 4b. Table 4a Table 4b Synthesis of EOMMA / ECPMA / α-GBLMA / aMMBL Copolymer Synthesis of triblock copolymer. (EOMMA / ECPMA / α-GBLMA / aMMBL)
[0156] The triblock copolymer 9 was prepared as follows. A monomer mixture of 11.5 g α-GBLMA, 12.7 g ECPMA, 7.6 g aMMBL and 3.2 g EOMMA was prepared. 11.0 g of the monomer mixture was combined with 5.5 g PGMEA and 148 mg V40 initiator to provide a feed solution. The feed solution was degassed and introduced into a syringe before use. In the reactor, 468 mg of 2-cyano-2-propyl dodecyl trithiocarbonate was used as a chain transfer agent (CTA) and protected at 115 ° C under N2. One third of the feed solution was added to the CTA and heated for 90 minutes; another one third of the feed solution was added to the CTA and heated for 90 minutes; and then the remaining feed solution was added to the CTA and heated for 120 minutes. When needed, an aliquot was taken from the reaction mixture under a gentle N2 flow. The block copolymer was separated by precipitation into isopropanol. It was found that the conversion reached> 90% at the end of each block polymerization. Synthesis of multi-block copolymers. (EOMMA / ECPMA / α-GBLMA / aMMBL)
[0157] Multi-block copolymer 10 was prepared as follows. A monomer mixture of 11.5 g α-GBLMA, 12.7 g ECPMA, 7.6 g aMMBL and 3.2 g EOMMA was prepared. 11.0 g of the monomer mixture was combined with 5.7 g PGMEA and 285 mg V40 initiator to provide a feed solution. The feed solution was degassed and introduced into a syringe before use. In the reactor, 397 mg of 2-cyano-2-propyl dodecyl trithiocarbonate was used as CTA and protected at 115 ° C under N2. About 1 / 9 of the feed solution was added to the CTA and heated for 60 minutes; this addition was repeated 8 times more, with heating between each subsequent addition of the feed solution. When needed, an aliquot was taken from the reaction mixture under a gentle N2 flow. The block copolymer was separated by precipitation into isopropanol. It was found that the conversion reached> 90% at the end of each block polymerization. Synthesis of tetrablock copolymer. (EOMMA / ECPMA / α-GBLMA / aMMBL)
[0158] Tetrablock copolymer 11 was prepared by a method similar to that used to prepare copolymers 9 and 10. Comparison of copolymers. (EOMMA / ECPMA / α-GBLMA / aMMBL)
[0159] Random Copolymer 8 (comparative) was prepared as follows. 6.3 g of a monomer mixture (EOMMA / ECPMA / α-GBLMA / aMMBL in a molar ratio of 10 / 30 / 30 / 30) was combined with 8.2 g of PGMEA and 711 mg of V601 initiator, and the mixture was degassed. After heating at 85° C. for 160 minutes, the copolymer was precipitated into isopropanol.
[0160] Block copolymers derived from the monomer combination EOMMA / ECPMA / α-GBLMA / aMMBL (10 / 30 / 30 / 30 molar ratio) and comparative copolymers are summarized in Table 5. Table 5 M w 、M n , and dispersion index Determined by GPC using polystyrene standards. Photoresist preparation.
[0161] Positive photoresist compositions PR12 to PR19 were prepared by dissolving the solid components (copolymer, PAG, quencher and additive) in a solvent using the materials and amounts indicated in Table 6, wherein the amounts are expressed in wt% based on 100wt% of the total weight of solids. The total solids content of the photoresist composition was 3.1%. The solvent system contained propylene glycol methyl ether acetate (S1) and methyl 2-hydroxyisobutyrate (S2). Each mixture was shaken on a mechanical shaker in a 100 mL glass container and filtered through a PTFE disc filter with a pore size of 0.20 microns. Table 6 Lithography Testing - Examples 31 to 54 E 尺寸 , EL%, LWR and PCM evaluation
[0162] Use 205℃ curing temperature with AR TM 40A antireflective agent (DuPont Electronics & Industries) was spin-coated on a 300 mm silicon wafer for 60 seconds to form a first BARC layer with a thickness of 80 nm. The AR TMThe wafer was spin coated with 104 antireflective agent (DuPont Electronics & Industries) for 60 seconds to form a second BARC layer with a thickness of 40 nm. The wafer was then spin coated with the corresponding photoresist composition from Table 6 and soft baked at 90° C. for 60 seconds to provide a photoresist layer with a thickness of 90 nm. The wafer was then spin coated with 104 antireflective agent (DuPont Electronics & Industries) for 60 seconds to form a second BARC layer with a thickness of 40 nm. The wafer was then spin coated with the corresponding photoresist composition from Table 6 and soft baked at 90° C. for 60 seconds to provide a photoresist layer with a thickness of 90 nm. TM LITHIUS TM The coating tool coated the BARC and photoresist layers. Using an ASML 1900i immersion scanner (1.35NA, 0.988 / 0.90 inner / outer σ, dipole illumination with 35Y polarization), the wafer was exposed to various doses of 193nm activating radiation using a mask with a line-space pattern (38nm line width / 76nm spacing, 37nm line width / 74nm spacing, 34nm line width / 74nm spacing, or 32nm line width / 74nm spacing). The exposed wafer was post-exposure baked at 95°C for 60 seconds and washed with 0.26N TMAH aqueous solution (MF TM -CD26, DuPont Electronics & Industries) for 12 seconds. The wafer was then rinsed with DI water and spin dried to form a photoresist pattern. CD line width measurements of the formed pattern were performed using a Hitachi High-Tech CG4000 CD-SEM.
[0163] The critical dimension (CD) of the line-space pattern in nanometers (nm) is analyzed, where the patterning energy “E 尺寸 ” is the irradiation energy when the CD of the formed line-space pattern is equal to the CD of the mask pattern. E 尺寸 mJ / cm 2 ). Exposure latitude (EL%) is the difference in exposure energy required to print a line-space pattern at plus or minus 10% of the target diameter, normalized by the set energy. Line width roughness (LWR) is expressed in nanometers (nm) and is determined as a 3-σ value from the distribution of a total of 100 arbitrary points of line width measurement, followed by removal of metrology noise. PCM is pattern collapse margin, which is expressed in nanometers. E 尺寸 , EL%, LWR and PCM data are shown in Table 7a, Table 7b and Table 7c. Table 7a Table 7b Table 7c Synthesis of IAM / α-GBLMA / HAMA Copolymer Synthesis of multi-block copolymers. (IAM / α-GBLMA / HAMA)
[0164] Multi-block copolymer 12 was prepared as follows. A monomer solution of 18.3 g IAM, 11.0 g HAMA, 19.3 g α-GBLMA and 24.5 g PGMEA was prepared. 12.3 g of the monomer solution was combined with 227 mg of V40 initiator as a feed solution. The feed solution was degassed and introduced into a syringe before use. In the reactor, 353 mg of 2-cyano-2-propyl dodecyl trithiocarbonate was used as CTA and protected at 110° C. under N2. About 1 / 8 of the feed solution was added to the CTA and heated for 60 minutes; this addition was repeated 7 more times, with heating after each subsequent addition. When necessary, an aliquot was taken from the reaction mixture under a gentle N2 flow. The block copolymer was separated by precipitation into isopropanol. It was found that the conversion reached>97% at the end of each block polymerization. Comparison of copolymers. (IAM / α-GBLMA / HAMA)
[0165] Comparative copolymer 13 was prepared as follows. A monomer solution of 18.3 g IAM, 11.0 g HAMA, 19.3 g α-GBLMA, and 24.5 g PGMEA was prepared. In a reactor, 153 mg 2-cyano-2-propyl dodecyl trithiocarbonate was used as CTA and combined with 7.7 g monomer solution, 15.3 g PGMEA, and 1520 mg V40 initiator. After degassing, the mixture was heated to 95 ° C for 26 hours, cooled to room temperature, and then precipitated into isopropanol.
[0166] Block copolymers derived from the monomer combination IAM / α-GBLMA / HAMA (30 / 50 / 20 molar ratio) and comparative copolymers are summarized in Table 8. Table 8 M w 、M n , and dispersion index Determined by GPC using polystyrene standards. Photoresist preparation.
[0167] Positive photoresist compositions PR20 to PR23 were prepared by dissolving the solid components (copolymer, PAG, quencher and additive) in a solvent using the materials and amounts indicated in Table 9, wherein the amounts are expressed in wt% based on 100wt% of the total weight of solids. The total solids content of the photoresist composition was 2.9%. The solvent system contained PGMEA (S1) and methyl 2-hydroxyisobutyrate (S2). Each mixture was shaken on a mechanical shaker in a 100 mL glass container and filtered through a PTFE disc filter having a pore size of 0.20 microns. Table 8 Lithography Testing - Examples 55 to 66 E 尺寸 , EL%, LWR and PCM evaluation
[0168] Use 205℃ curing temperature with AR TM 40A antireflective agent (DuPont Electronics & Industries) was spin-coated on a 300 mm silicon wafer for 60 seconds to form a first BARC layer with a thickness of 80 nm. The AR TM The wafer was spin coated with 104 antireflective agent (DuPont Electronics & Industries) for 60 seconds to form a second BARC layer with a thickness of 40 nm. The wafer was then spin coated with the corresponding photoresist composition from Table 6 and soft baked at 90° C. for 60 seconds to provide a photoresist layer with a thickness of 90 nm. The wafer was then spin coated with 104 antireflective agent (DuPont Electronics & Industries) for 60 seconds to form a second BARC layer with a thickness of 40 nm. The wafer was then spin coated with the corresponding photoresist composition from Table 6 and soft baked at 90° C. for 60 seconds to provide a photoresist layer with a thickness of 90 nm. TM LITHIUS TM The coating tool coated the BARC and photoresist layers. Using an ASML 1900i immersion scanner (1.35NA, 0.988 / 0.90 inner / outer σ, dipole illumination with 35Y polarization), the wafer was exposed to various doses of 193nm activating radiation using a mask with a line-space pattern (38nm line width / 76nm spacing, 37nm line width / 74nm spacing, 34nm line width / 74nm spacing, or 32nm line width / 74nm spacing). The exposed wafer was post-exposure baked at 95°C for 60 seconds and washed with 0.26N TMAH aqueous solution (MF TM -CD26, DuPont Electronics & Industries) for 12 seconds. The wafer was then rinsed with DI water and spin dried to form a photoresist pattern. CD line width measurements of the formed pattern were performed using a Hitachi High-Tech CG4000 CD-SEM.
[0169] The critical dimension (CD) of the line-space pattern in nanometers (nm) is analyzed, where the patterning energy “E 尺寸 ” is the irradiation energy when the CD of the formed line-space pattern is equal to the CD of the mask pattern. E尺寸 mJ / cm 2 ). Exposure latitude (EL%) is the difference in exposure energy required to print a line-space pattern at plus or minus 10% of the target diameter, normalized by the set energy. Line width roughness (LWR) is expressed in nanometers (nm) and is determined as a 3-σ value from the distribution of a total of 100 arbitrary points of line width measurement, followed by removal of metrology noise. PCM is pattern collapse margin, which is expressed in nanometers. E 尺寸 , EL%, LWR and PCM data are shown in Table 9a, Table 9b and Table 9c. Table 9a Table 9b Table 9c Synthesis of CHOMMA / α-GBLMA / NLMA Copolymer Synthesis of triblock copolymer. (CHOMMA / α--GBLMA / NLMA)
[0170] Multi-block copolymer 14 was prepared as follows. A monomer solution of 9.5 g α-GBLMA, 11.1 g CHOMMA and 6.2 g NLMA in 17.9 g 1,4-dioxane was prepared. 10.0 g of the monomer solution was mixed with 82 mg V601 initiator as a feed solution. The feed solution was degassed and introduced into a syringe before use. In the reactor, 247 mg of 2-cyano-2-propyl dodecyl trithiocarbonate was used as CTA and protected at 85 ° C under N2. One-third of the feed solution was added to the CTA and heated for 120 minutes; another one-third of the feed solution was added to the reactor and heated to 85 ° C for another 120 minutes; and the remaining feed solution was added to the reactor at 85 ° C and reacted for 150 minutes. When needed, an aliquot was taken from the reaction mixture under a gentle N2 flow. It was found that the conversion rate was >97%. The reaction mixture was diluted with PGMEA and precipitated into isopropanol. Synthesis of tetrablock copolymer (CHOMMA / α-GBLMA / NLMA)
[0171] Multi-block copolymer 15 was prepared using a procedure similar to that used to prepare copolymer 14. Comparison of copolymers. (CHOMMA / α-GBLMA / NLMA)
[0172] Random copolymer 16 (comparative) was prepared following a similar procedure as copolymer 8 using a monomer molar ratio of 40 / 40 / 20.
[0173] Block copolymers derived from the monomer combination CHOMMA / α-GBLMA / NLMA (40 / 40 / 20 molar ratio) and comparative copolymers are summarized in Table 10. Table 10 M w 、M n , and dispersion index Determined by GPC using polystyrene standards. Photoresist preparation
[0174] Positive photoresist compositions PR24 to PR29 were prepared by dissolving the solid components (copolymer, PAG, quencher and additive) in a solvent using the materials and amounts indicated in Table 11, wherein the amounts are expressed in wt% based on 100wt% of the total weight of solids. The total solids content of the photoresist composition was 2.9%. The solvent system contained PGMEA (S1) and methyl 2-hydroxyisobutyrate (S2). Each mixture was shaken on a mechanical shaker in a 100 mL glass container and filtered through a PTFE disc filter having a pore size of 0.20 microns. Table 11 Lithography Testing - Examples 67 to 91 E 尺寸 , EL%, LWR and PCM evaluation
[0175] Use 205℃ curing temperature with AR TM 40A antireflective agent (DuPont Electronics & Industries) was spin-coated on a 300 mm silicon wafer for 60 seconds to form a first BARC layer with a thickness of 80 nm. The AR TM The wafer was spin coated with 104 antireflective agent (DuPont Electronics & Industries) for 60 seconds to form a second BARC layer with a thickness of 40 nm. The wafer was then spin coated with the corresponding photoresist composition from Table 11 and soft baked at 90° C. for 60 seconds to provide a photoresist layer with a thickness of 90 nm. The wafer was then spin coated with 104 antireflective agent (DuPont Electronics & Industries) for 60 seconds to form a second BARC layer with a thickness of 40 nm. The wafer was then spin coated with the corresponding photoresist composition from Table 11 and soft baked at 90° C. for 60 seconds to provide a photoresist layer with a thickness of 90 nm. TM LITHIUS TMThe coating tool coated the BARC and photoresist layers. Using an ASML 1900i immersion scanner (1.35NA, 0.988 / 0.90 inner / outer σ, dipole illumination with 35Y polarization), the wafer was exposed to various doses of 193nm activating radiation using a mask with a line-space pattern (38nm line width / 76nm spacing, 37nm line width / 74nm spacing, 34nm line width / 74nm spacing, or 32nm line width / 74nm spacing). The exposed wafer was post-exposure baked at 95°C for 60 seconds and washed with 0.26N TMAH aqueous solution (MF TM -CD26, DuPont Electronics & Industries) for 12 seconds. The wafer was then rinsed with DI water and spin dried to form a photoresist pattern. CD line width measurements of the formed pattern were performed using a Hitachi High-Tech CG4000 CD-SEM.
[0176] The critical dimension (CD) of the line-space pattern in nanometers (nm) is analyzed, where the patterning energy “E 尺寸 ” is the irradiation energy when the CD of the formed line-space pattern is equal to the CD of the mask pattern. E 尺寸 mJ / cm 2 ). Exposure latitude (EL%) is the difference in exposure energy required to print a line-space pattern at plus or minus 10% of the target diameter, normalized by the set energy. Line width roughness (LWR) is expressed in nanometers (nm) and is determined as a 3-σ value from the distribution of a total of 100 arbitrary points of line width measurement, followed by removal of metrology noise. PCM is pattern collapse margin, which is expressed in nanometers. E 尺寸 , EL%, LWR and PCM data are shown in Table 12a, Table 12b and Table 12c. Table 12a Table 12b Table 12c Table 12d
[0177] While the disclosure has been described in connection with what are presently considered to be practical exemplary embodiments, it is to be understood that the invention is not limited to the disclosed embodiments, but, on the contrary, is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.
Claims
1. A block copolymer comprising: a first block comprising two or more structurally different repeating units; a second block comprising two or more structurally different repeating units; The repeating units of the first block contain an acid-labile group, a lactone group, a salt group, or a hydroxyaryl group; and The repeating units of the second block contain an acid-labile group, a lactone group, a salt group, or a hydroxyaryl group, wherein the two or more structurally different repeating units of the first block are the same as the two or more structurally different repeating units of the second block.
2. The block copolymer according to claim 1, wherein The two or more structurally different repeating units of the first block and the two or more structurally different repeating units of the second block are present in the first block and the second block in substantially the same ratio, and each block has the same structural unit gradient direction from the first end to the second end of the block.
3. The block copolymer according to claim 1 or 2, wherein The first block and the second block each include a repeating unit including an acid-labile group.
4. The block copolymer according to any one of claims 1 to 3, wherein The first block and the second block each include a repeating unit containing a lactone group or a salt group.
5. The block copolymer according to any one of claims 1 to 4, wherein The average number of repeating units within each block is 5 or more.
6. The block copolymer according to any one of claims 1 to 5, wherein The average number of blocks in the block copolymer is 3 to 10. 7 . The block copolymer according to claim 1 , further comprising a block having no structurally different repeating units that are the same as the first block and the second block.
8. A polymer comprising one or more block copolymers as claimed in any one of claims 1 to 7 bonded to another part of the polymer. 9 . A photoresist composition comprising the block copolymer according to claim 1 and a solvent.
10. A pattern forming method, comprising: forming a photoresist composition layer on a substrate from the photoresist composition according to claim 9; exposing the photoresist composition layer to activating radiation in a pattern-wise manner; as well as The exposed photoresist composition layer is developed to provide a resist relief image.
Citation Information
Patent Citations
Radiation-sensitive copying composition
US4189323A
Processes based on atom (or group) transfer radical polymerization and novel (co)polymers having useful structures and properties
US6887962B2
Compound, resin, resist composition and method for producing resist pattern
US8431325B2